Adhesive composite material for improved attachment and detachment performance

JP2026534535APending Publication Date: 2026-10-16WL GORE & ASSOC INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026519936
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-02
Filing Date
2024-10-02
Publication Date
2026-10-16

Smart Images

  • Figure 2026534535000001_ABST
    Figure 2026534535000001_ABST
Patent Text Reader

Abstract

Systems, articles, and methods relating to adsorbent composites, such as those used in gas separation processes mediated by thermal swing adsorption, are disclosed. The adsorbent composite comprises an adsorbent filler and a microwave-permeable binder, wherein the adsorbent composite is in the form of a sheet, and the sheet has a structure that facilitates the narrowing of parallel channels of fluid flow. The adsorbent composite may have an adsorbent filler embedded in the microstructure of the binder, such as an expandable microwave-permeable polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Cross-reference of related applications This application claims priority to Provisional Application No. 63 / 541,970, filed on 2 October 2023, the contents of which said Provisional Application are incorporated in full by reference herein for all purposes.

[0002] field This disclosure generally relates to adsorbent composites, processes, and systems for the adsorption and desorption of substances such as compounds from fluid flows. [Background technology]

[0003] background Thermal swing adsorption (TSA) is a process that separates gaseous components by utilizing periodic fluctuations in temperature and pressure. This process can be used to separate specific substances, such as target compounds, from gaseous mixtures in a fluid flow. TSA can be divided into several stages, including an adsorption stage in which adsorbates are captured on an adsorbent material, and a desorption stage in which the captured adsorbates are removed from the adsorbent material (for example, for recovery). The adsorption stage of TSA condenses and captures gas molecules at relatively low temperatures, while the desorption stage requires energy to heat the adsorbent material to facilitate the release of the captured compounds.

[0004] The process of heating adsorbent materials to induce desorption of captured target substances is a major energy source in TSA processes, and current methods, systems, and materials contribute to the wasted time and energy of this process. Microwave heating is one option to accelerate the process and reduce the amount of energy required for desorption. However, solid adsorbent materials such as pure adsorbent powders do not exhibit binding properties under such conditions. Solid adsorbent materials such as activated carbon, zeolites, silica, and metal-organic structures must be processed into structured forms to facilitate adsorption / desorption upon exposure to microwave irradiation. Structures are often supplied in the form of binders such as bentonite, attapulgite, kaolin, alumina, and silica, which are commonly used. However, these binder materials may absorb microwave energy, reducing the amount of microwave irradiation absorbed by the adsorbent material and requiring more energy input to achieve desorption. Therefore, various aspects of TSA, including the efficiency of the desorption stage, need to be improved to increase the overall efficiency of the process. [Overview of the Initiative]

[0005] Abstract This abstract provides a high-level overview of various embodiments and introduces some of the concepts that will be further explained in the "Detailed Description" section below. This subject matter should be understood by referring to the entire specification, some or all of the drawings, and the appropriate parts of each claim.

[0006] According to one embodiment (Embodiment 1), the disclosure relates to an adsorbent composite, for example, an adsorbent composite used in a microwave temperature swing adsorption (TSA) process, comprising an adsorbent filler and a microwave-transparent binder, wherein the microwave-transparent binder has a dielectric loss coefficient of 0.0001 to 0.1. Here, "microwave-transparent" refers to a material through which microwaves pass or are transmitted with minimal strain. In some examples, the properties can be described by the dielectric loss coefficient (ε”) and dielectric constant (ε') when microwave energy is applied, for example, in the frequency range of 300 MHz to 300 GHz.

[0007] Embodiment 2 is an adsorbent composite material in which the microwave-permeable binder contains a polymer. Embodiment 3 is the adsorbent composite material according to Embodiment 2, wherein the polymer includes a hydrocarbon polymer, a fluoropolymer, a polyolefin, or a combination thereof.

[0008] Embodiment 4 is an adsorbent composite material according to Embodiment 3, wherein the polyolefin comprises a compound selected from the group consisting of polyethylene, polypropylene, ethylenepropylene diene terpolymer, random copolymers containing at least one propylene group, at least one ethylene group, and at least one butene group and / or at least one hexene group, and combinations thereof.

[0009] Embodiment 5 is an adsorbent composite material described in Embodiment 2, wherein the polymer is polybenzimidazole (PBI), polyamide-imide (PAI), polyimide (PI), polyethersulfone (PES), fluorinated ethylene propylene (FEP), polyetherimide (PEI), polysulfone (PSU), polyamide (PA), cellulose, methylcellulose, cellulose ester, polystyrene (PS), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA or PVOH), polyvinyl butyral (PVB), polyvinyl chloride (PVC), polyvinylpyrrolidone (PVP), polyphenylene sulfide This includes compounds selected from the group consisting of (PPS), polyfluoroethylene propylene (PFEP), polyperfluoroacrylate (PPFA), polyvinylidene fluoride (PVDF), terpolymer of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride (THV), polychlorotrifluoroethylene (PCFE), poly(ethylene-co-tetrafluoroethylene) (ETFE), ultra-high molecular weight polyethylene (UHMWPE), polyparaxylylene (PPX), polylactic acid (PLLA), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), cyclic olefin polymer (COP), cyclic olefin copolymer (COC), their expanded derivatives, and combinations thereof.

[0010] Embodiment 6 is an adsorbent composite material according to any one of Embodiments 2 to 5, wherein the polymer includes a compound selected from the group consisting of cellulose, polytetrafluoroethylene (PTFE), polyethylene (PE), polypropylene (PP), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyamideimide (PAI), and polyimide (PI).

[0011] Embodiment 7 is an adsorbent composite material according to any one of Embodiments 2 to 6, wherein the polymer has a dielectric constant of 1.5 to 4.

[0012] Embodiment 8 is an adsorbent composite material according to any one of Embodiments 1 to 7, wherein the adsorbent composite material includes a parallel-passage type contactor structure comprising one or more self-supporting adsorbent sheets and substantially parallel raised portions.

[0013] Embodiment 9 is an adsorbent composite material according to Embodiment 8, wherein one or more self-supporting adsorbent sheets are arranged in multiple overlapping layers, and these layers are spaced apart by substantially parallel ridges so that gas can flow between the layers.

[0014] Embodiment 10 is an adsorbent composite material according to Embodiment 8 or 9, wherein the adsorbent composite material has embossed raised portions.

[0015] Embodiment 11 is an adsorbent composite material according to any one of Embodiments 8 to 10, wherein each of the one or more self-supporting adsorbent sheets has a thickness of 0.1 to 10 mm and a width of 30 to 1000 mm.

[0016] Embodiment 12 is an adsorbent composite material according to any one of Embodiments 1 to 11, wherein the microwave-transmitting binder comprises fibrils or a microstructure comprising fibrils and nodes.

[0017] Embodiment 13 is an adsorbent composite material according to any one of Embodiments 9 to 12, wherein the adsorbent filler is partially or completely embedded in the spaces between a plurality of overlapping layers and / or in at least a portion of the microstructure of the microwave-transparent binder.

[0018] Embodiment 14 is an adsorbent composite material according to any one of Embodiments 1 to 13, and contains the adsorbent filler in an amount of 10% to 95% (w / w) relative to the total weight of the adsorbent composite material.

[0019] Embodiment 15 is an adsorbent composite material according to any one of Embodiments 1 to 14, wherein the adsorbent composite material has a total porosity of 30% to 95%.

[0020] Embodiment 16 is the adsorptive composite material according to any one of Embodiments 1 to 15, wherein the adsorbent filler comprises a high-loss dielectric material (loss tangent greater than 0.1), a low-loss dielectric material (loss tangent less than 0.1), or a combination thereof.

[0021] Embodiment 17 is the adsorptive composite material according to any one of Embodiments 1 to 16, wherein the adsorbent filler comprises at least one amine group, activated carbon, carbon, graphene oxide, graphite, silica, metal-organic framework, zeolite, alumina, alkali metal oxide, polymeric sorbent, alkali carbonate, ion exchange resin, polyethyleneimine, or a combination thereof.

[0022] Embodiment 18 is the adsorptive composite material according to Embodiment 17, wherein the adsorbent filler comprising at least one amine group comprises an impregnated amine, an amine supported on a polymer, an amine supported on a metal oxide, an amine supported on carbon, an amine-functionalized polymer, or a combination thereof.

[0023] Embodiment 19 is the adsorptive composite material according to any one of Embodiments 1 to 18, wherein the adsorptive composite material does not comprise a mineral binder.

[0024] Embodiment 20 is the adsorptive composite material according to Embodiment 19, wherein the mineral binder comprises a mineral selected from the group consisting of natural clay, bentonite, attapulgite, kaolin, alumina, silica, gypsum, and combinations thereof.

[0025] According to a twenty-first embodiment (Embodiment 21), the present disclosure relates to a method for desorbing an adsorbate from an adsorption unit comprising the adsorptive composite material according to any one of Embodiments 1 to 20, wherein the method comprises irradiating the adsorption unit with an electromagnetic wave having a frequency of 1 MHz to 300 GHz, the adsorbate is adsorbed on the adsorptive composite material, and the irradiation promotes desorption of the adsorbate from the adsorptive composite material.

[0026] Embodiment 22 is the method described in Embodiment 21, wherein the irradiation includes subjecting the adsorbent composite material to microwave irradiation in the frequency range of 300 MHz to 300 GHz.

[0027] Embodiment 23 is the method described in Embodiment 21, wherein the irradiation includes subjecting the adsorbent composite material to radio frequency (RF) heating in the frequency range of 1 MHz to 300 MHz.

[0028] Embodiment 24 is the method described in any one of Embodiments 21 to 23, wherein the adsorbent composite material is housed within the adsorption unit.

[0029] Embodiment 25 is a method according to any one of Embodiments 21 to 24, wherein the adsorbate is hydrogen gas (H2), methane (CH4), carbon monoxide (CO), carbon dioxide (CO2), water (H2O), nitrogen oxides (NO2). x ), sulfur oxides (SO x ), volatile organic compounds (VOCs), or combinations thereof.

[0030] In the 26th embodiment (Embodiment 26), the disclosure relates to a method for processing a fluid flow, comprising bringing the fluid flow into contact with a device comprising an adsorbent composite material according to any one of Embodiments 1 to 20, wherein the fluid flow has a temperature of at least -50°C, a surface velocity of 0.1 to 2.0 meters / second, and experiences a pressure drop of 0.25 to 5 kPa per meter of the adsorbent composite material.

[0031] Embodiment 27 is the method described in Embodiment 26, wherein the fluid flow has a dew point of at least -120°C.

[0032] Embodiment 28 is the method described in Embodiment 26 or 27, further comprising irradiating the device with electromagnetic waves having a frequency of 1 MHz to 300 GHz, and desorbing the adsorbate.

[0033] Embodiment 29 is a method according to any one of Embodiments 26 to 28, wherein the adsorbate includes a compound selected from the group consisting of hydrogen gas (H2), carbon monoxide (CO), carbon dioxide (CO2), water (H2O), nitrous oxide (N2O), nitric oxide (NO), dinitrogen trioxide (N2O3), nitrogen dioxide (NO2), dinitrogen pentoxide (N2O5), dinitrogen tetroxide (N2O4), sulfur dioxide (SO2), sulfur trioxide (SO3), volatile organic compounds (VOCs), and combinations thereof, and each compound is present at a concentration of at least 10 ppb.

[0034] Embodiment 30 is the method described in Embodiment 25 or 29, wherein the VOC is selected from the group consisting of benzene, ethylene glycol, formaldehyde, methylene chloride, tetrachloroethylene, toluene, xylene, acetaldehyde, ethane, propane, and 1,3-butadiene.

[0035] The 31st embodiment (Embodiment 31) relates to a system for adsorbing and desorbing an adsorbate, comprising an inlet opening for introducing a fluid flow into the system, an adsorption unit containing an adsorbent composite material as described in any one of Embodiments 1 to 20, a microwave unit housing the adsorption unit (the microwave unit is used to irradiate the adsorption unit with microwaves, thereby promoting the desorption of the adsorbent from the adsorption unit), and an outlet opening.

[0036] Embodiment 32 is the system described in Embodiment 31, wherein the adsorption unit includes columns. Embodiment 33 is the system described in Embodiment 31, wherein the adsorption unit includes a plurality of columns. Embodiment 34 is the system described in Embodiment 33, wherein the adsorption unit includes a column array. Embodiment 35 is the system described in Embodiment 33, wherein the column array is in a shell-and-tube configuration or a laminated sheet configuration.

[0037] Embodiment 36 is the system according to any one of Embodiments 31 to 35, wherein the adsorption unit further includes at least one fluid inlet and at least one fluid outlet, such as for introducing a fluid to regulate the temperature of the system.

[0038] Embodiment 37 is the system according to any one of Embodiments 31 to 36, wherein the inlet opening is a fluid inlet and the outlet is a fluid outlet. Embodiment 38 is the system according to Embodiment 31, wherein the adsorption unit includes a plurality of inlets and / or a plurality of outlets. Embodiment 39 is the system according to Embodiment 39, wherein the plurality of inlet openings include a plurality of fluid inlets and the plurality of outlet openings include a fluid outlet.

[0039] In the foregoing, the invention of this application has been described both in general terms and in terms of specific embodiments. It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments without departing from the scope of the disclosure. Accordingly, the embodiments described herein are intended to encompass modifications and variations of the invention, insofar as they fall within the scope of the appended claims and their equivalents. [Brief explanation of the drawing]

[0040] Brief explanation of the drawing The accompanying drawings are included to enhance the understanding of this disclosure, are incorporated herein, constitute part thereof, illustrate embodiments, and illustrate the principles of this disclosure together with the description.

[0041] [Figure 1] Figure 1 is a schematic diagram of a non-limiting embodiment of an adsorbent composite material including an adsorbent filler and a microwave-transparent binder.

[0042] [Figure 2A] Figure 2A shows a SEM image of a cross-sectional view of a non-limiting embodiment of the adsorbent composite material described herein (including 3A zeolite and stretched PTFE (ePTFE) as a microwave-transparent binder).

[0043] [Figure 2B] Figure 2B shows an SEM image of a cross-sectional view of an additional, non-limiting embodiment of the adsorbent composite described herein (including 5A zeolite and ePTFE as a microwave-transmissive binder).

[0044] [Figure 2C] Figure 2C shows a SEM image of a cross-sectional view of an additional, non-limiting embodiment of the adsorbent composite described herein (including silica and ePTFE as a microwave-permeable binder).

[0045] [Figure 3] Figure 3 shows a cross-sectional SEM image of a non-limiting embodiment of an adsorbent composite material comprising 13X zeolite and ePTFE as a microwave-transparent binder, as described herein.

[0046] [Figure 4] Figure 4 shows an additional, non-limiting embodiment of the adsorbent composite described herein, in which the sheet of adsorbent composite is wound in a helical shape.

[0047] [Figure 5A] Figure 5A shows a non-limiting embodiment of an adsorbent composite material containing an adsorbent filler and ePTFE.

[0048] [Figure 5B] Figure 5B shows an adsorbent containing zeolite beads according to a comparative example.

[0049] [Figure 6] Figure 6 shows an exemplary adsorption / desorption apparatus having a microwave unit, a gas inlet, an adsorption column containing a structured adsorbent including a microwave-permeable binder, and a gas outlet.

[0050] [Figure 7] Figure 7 shows an exemplary adsorption unit having a fluid inlet, fluid outlet, fluid inlet opening, fluid outlet opening, and adsorption column.

[0051] [Figure 8] Figure 8 is a line graph showing the column airflow resistance in units of differential pressure (kPa) per meter length for additional non-limiting embodiments of the adsorbent composite material containing 3A zeolite and ePTFE as described herein, and for adsorbents containing 3A zeolite beads according to comparative examples.

[0052] [Figure 9] Figure 9 is a bar graph showing the amount of water (H2O) desorbed after microwave irradiation from an adsorbent containing zeolite beads along with a microwave-absorbing binder, according to additional non-limiting embodiments of the adsorbent composite material containing 13X zeolite and ePTFE as described herein, and comparative examples.

[0053] [Figure 10] Figure 10 is a bar graph showing the amount of CO2 (mmol / g) desorbed after various microwave irradiation times from an adsorbent containing 13X zeolite beads together with a microwave-absorbing binder, according to additional non-limiting embodiments of the adsorbent composite containing 13X zeolite and ePTFE as described herein, and comparative examples. The irradiation times are: Group 1: 75 seconds, Group 2: 75 seconds + 60 seconds, Group 3: 75 seconds + 60 seconds + 60 seconds.

[0054] [Figure 11] Figure 11 is a bar graph showing the amount (%) of desorbed water (H2O) from additional non-limiting embodiments of adsorbent composite materials containing silica and ePTFE as described herein. [Modes for carrying out the invention]

[0055] Detailed explanation In addition to the disclosed advantages and improvements, other purposes and merits of this disclosure will become apparent from the following description, together with the accompanying drawings. While this specification discloses detailed embodiments of this disclosure, it should be understood that the disclosed embodiments are merely illustrative of the various forms in which the disclosure can be implemented. Furthermore, each example relating to the various embodiments of this disclosure is intended to be illustrative and not limiting.

[0056] This disclosure is not intended to be confined to any particular purpose. For example, terms used in this application should be interpreted broadly in the context of the meanings that experts in the art assign to such terms.

[0057] Definitions and Terms Throughout the specification and claims, unless the context clearly indicates otherwise, the following terms have the meanings expressly associated herein. The phrases “in one embodiment,” “in an embodiment,” and “in several embodiments” may refer to the same embodiment, but not necessarily the same embodiment. Furthermore, the phrases “in another embodiment” and “in several other embodiments” may refer to different embodiments, but not necessarily different embodiments. All embodiments of this disclosure are intended to be combinable without departing from the scope or spirit of the disclosure.

[0058] With regard to terms relating to inaccuracy, the terms “approximately” and “generally” can be used interchangeably to refer to measurements that include both the stated measurement and measurements that are reasonably close to the stated measurement. A measurement that is reasonably close to the stated measurement deviates by a reasonably small amount from the stated measurement to the extent that it can be understood and readily verified by a person skilled in the art in the relevant field. Such deviations may result, for example, from measurement errors, calibration differences in measurement and / or manufacturing equipment, human error in reading and / or setting of measurements, fine-tuning made to optimize performance and / or structural parameters to account for measurement differences related to other components, specific implementation scenarios, improper adjustment and / or handling of the object by a person or machine, and / or similar. If a person skilled in the art in the relevant field determines that the value of such a reasonably small difference cannot be readily verified, the terms “approximately” and “generally” can be understood to mean plus or minus 10% of the stated value.

[0059] As used herein, the term “between” does not necessarily require that an element be directly adjacent to another element. Generally, the term means a configuration in which something is sandwiched between two or more other things. At the same time, the term “between” can also describe something that is directly adjacent to two opposing objects. Thus, in any one or more embodiments disclosed herein, a particular structural element positioned between two other structural elements may take one of the following configurations:

[0060] It is positioned directly between both of the other structural elements, and is positioned such that a particular structural element is in direct contact with both of the other structural elements.

[0061] It is positioned directly adjacent to one of the two other structural elements, and is positioned such that a particular structural element is in direct contact with only one of the two other structural elements.

[0062] It was positioned indirectly adjacent to one of the two other structural elements, and the particular structural element was not in direct contact with only one of the two other structural elements, but rather positioned such that there was another element that placed the particular structural element next to one of the two other structural elements.

[0063] It is indirectly positioned between two other structural elements, and the particular structural element does not directly contact either of the other two structural elements, and other features are positioned between them, or

[0064] Any combination of these.

[0065] When used herein, the term “based on” is not restrictive and may also refer to additional elements not listed unless clearly indicated otherwise in the context. Furthermore, throughout this specification, “a,” “an,” and “the” include their plural forms. “In” includes “in” and “on.”

[0066] As used herein, the terms “adsorbent” and “adsorbent” are interchangeable and refer to substances having the property of collecting molecules of other substances by absorption, adsorption, or at least one of a combination thereof. Examples of adsorbent materials in adsorbent composites, such as adsorbent fillers, include activated carbon, coal-derived carbon, lignite-derived carbon, wood-derived carbon, coconut-derived carbon, alumina, alkali metal oxides, metal-organic structures, polymer adsorbents, alkali carbonates, ion exchange resins, polyethyleneimines, silica, silica gel, zeolites, impregnated amines, amines supported on polymers, amines supported on metal oxides, amines supported on carbon, amine-functionalized polymers, or any combination thereof. In some embodiments, the polymer adsorbent is benzylamine-functionalized polystyrene.

[0067] In this specification, "composite material" refers to a material comprising two or more constituent materials having different physical or chemical properties, and the combination of these constituent materials results in a material having properties different from those of the individual components.

[0068] As used herein, “adsorbent composite” refers to a composite comprising an adsorbent filler and a microwave-permeable binder. In embodiments, the microwave-permeable material, such as the microwave-permeable binder, may have a dielectric loss coefficient of about 0.0001 to about 0.1. In embodiments, the adsorbent composite may include an adsorbent filler containing adsorbent particles incorporated into the microstructure of the microwave-permeable binder, for example, by being embedded or entangled. In embodiments, the adsorbent filler may include a high-loss dielectric material (loss loss tangent greater than 0.1), a low-loss dielectric material (loss loss tangent less than 0.1), or a combination thereof. In embodiments, the adsorbent composite may not include a mineral binder having microwave absorption activity.

[0069] As used herein, the term "microwave-transparent" refers to a material that transmits microwaves with minimal distortion, such as by not substantially absorbing or reflecting microwaves. A "microwave-transparent" material can be described by its dielectric loss coefficient (ε”) and dielectric constant (ε') when energy is applied in the microwave frequency range (300 MHz to 300 GHz). The microwave penetration depth (Pd) is calculated according to Equation 1, where λ represents the wavelength.

[0070]

number

[0071] In the context of microwave irradiation applications, materials with a low dielectric loss coefficient can transmit more microwave energy without absorption compared to materials with a high dielectric loss coefficient, thus minimizing heat loss.

[0072] Alternatively, "microwave-transparent" materials can be described by their reflectance and / or transmission coefficients, which are determined in the microwave frequency range. The reflectance coefficient is used to define the reflected wave relative to an incident wave, such as when two different materials come into contact at an interface, like air and a microwave-transparent material. Considering a reflectance coefficient in the range of 0 to 1, a lower value indicates less reflection compared to a higher value.

[0073] The transmission coefficient represents the ratio of the transmitted particle current to the incident particle current when two different materials come into contact at the interface, including the amplitude, intensity, or total power of the transmitted wave relative to the incident wave. Considering transmission coefficients in the range of 0 to 1, a higher value indicates greater transmission compared to a lower value.

[0074] The reflection coefficient and transmission coefficient can be determined by various methods available in the art, including, for example, the use of microwave and radio frequency technologies, including vector network analyzers.

[0075] For reference, some representative materials recognized as having "microwave permeability" include perfluoroalkoxyalkanes (PFA), fluorinated ethylene propylene (FEP), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethylene (PE), and polypropylene (PP).

[0076] In contrast, "microwave absorptive" refers to materials that efficiently absorb microwaves and convert microwave energy into heat. This absorption and energy conversion reduces the intensity or reflectivity of the irradiated microwaves.

[0077] When microwave absorption occurs, the conversion of electromagnetic energy into heat depends on the relationship between the dielectric loss coefficient (ε”) and the dielectric constant (ε') of a given material. This relationship is known as the dissipation factor (or loss tangent, tanδ = ε”) / ε'). The higher the dielectric loss tangent of a material, the higher its microwave absorption and the narrower the microwave transmission range. Materials with a loss tangent greater than 0.1 are considered high-loss dielectric materials.

[0078] As used herein, the term “polymer” refers to one or more homopolymers, copolymers, or terpolymers. In non-limiting examples, polymers may include hydrocarbon polymers, fluoropolymers, polyolefins, or combinations thereof. In embodiments, the polymer may be an expanded (expanded, swelled, stretched, or foamed) polymer containing pores, as opposed to an unexpanded polymer.

[0079] As used herein, the terms “embedded” and “entangled” refer to a state in which the first material is distributed throughout the second material.

[0080] As used herein, the term “fluid flow” refers to a continuous flow of gas, liquid, or a combination thereof, such as within a system, apparatus, or adsorption unit as described herein. In some embodiments, the fluid flow includes a gaseous phase, such as a gaseous flow, a liquid phase, or a combination thereof. In some embodiments, the fluid flow may include distinct phases, such as a combination of a gaseous and a liquid phase. In some embodiments, the phases of the fluid flow are homogeneous and may consist entirely of gas, for example. In some embodiments, the fluid flow may include at least one distinct chemical component. In some embodiments, the fluid flow may include a chemically distinct combination of gas and / or vaporized liquid. In some embodiments, the fluid flow includes a fluid gas flow.

[0081] As used herein, the term “flue gas flow” refers to a gas mixture that may contain at least one byproduct of a combustion process (e.g., a coal combustion process, but not limited to such processes). In some embodiments, a flue gas flow may consist solely of byproducts of a combustion process. In some embodiments, a flue gas flow may contain at least one gas at a higher concentration than that produced by the combustion process. For example, in one non-limiting example, a flue gas flow may be subjected to a “scrubbing” process, in which water vapor may be added to the flue gas flow. Thus, in some such embodiments, a flue gas flow may contain water vapor at a higher concentration than the initial water vapor concentration from combustion. Similarly, in some embodiments, a flue gas flow may contain at least one gas at a lower concentration than the initial concentration of at least one gas discharged from the combustion process. This may occur, for example, by removing at least a portion of at least one gas after combustion. In some embodiments, a flue gas flow may take the form of a gas mixture that is a combination of byproducts of multiple combustion processes.

[0082] As used herein, the term “nitrogen oxides” refers to any nitrogen oxide. In some non-limiting embodiments, “nitrogen oxides” may specifically refer to gaseous nitrogen oxides that are known environmental pollutants. Non-limiting examples of nitrogen oxide compounds include nitrous oxide (N2O), nitric oxide (NO), dinitrogen trioxide (N2O3), nitrogen dioxide (NO2), dinitrogen pentoxide (N2O5), and dinitrogen tetroxide (N2O4).

[0083] As used herein, the term “sulfur oxide” refers to any sulfur oxide. In some embodiments, “sulfur oxide” may specifically refer to gaseous sulfur oxides known as environmental pollutants. Non-limiting examples of sulfur oxide compounds include sulfur dioxide (SO2) and sulfur trioxide (SO3). Other non-limiting examples of sulfur oxides include sulfur monoxide (SO), disulfur monoxide (S2O), and disulfur dioxide (S2O2).

[0084] As used herein, the terms “volatile organic compound” and “VOC” refer to organic compounds that have a high vapor pressure at room temperature. In some embodiments, “VOC” may specifically refer to volatile organic compounds known as environmental pollutants. Non-limiting examples of VOCs include benzene, ethylene glycol, formaldehyde, methylene chloride, tetrachloroethylene, toluene, xylene, acetaldehyde, ethane, propane, and 1,3-butadiene.

[0085] All prior patents and publications referenced herein are incorporated herein in their entirety by reference.

[0086] Description of various embodiments Those skilled in the art will readily understand that various aspects of this disclosure can be realized by countless methods and apparatus configured to perform the intended functions. It should also be noted that the accompanying drawings referenced herein are not necessarily drawn to scale and may be exaggerated to illustrate various aspects of this disclosure; in this respect, the drawings should not be construed as limiting.

[0087] The adsorbent composites disclosed herein can be used in a wide range of applications where improved desorption efficiency is desired, such as the removal of adsorbate from adsorbent materials in temperature swing adsorption processes. In some embodiments, the adsorbent composites may include an adsorbent filler and a microwave-permeable binder. Furthermore, articles comprising adsorbent composites are disclosed herein.

[0088] Figure 1 shows a non-limiting embodiment of an adsorbent composite, as described herein, comprising an adsorbent filler and a microwave-permeable binder such as a polymer. In this configuration, the adsorbent material, such as the adsorbent filler 102 (e.g., activated carbon, alumina, or zeolite), is partially or completely incorporated into the microstructure of the polymer material 104 (e.g., the node structure of expanded PTFE) to form the adsorbent composite 100. In other embodiments, the adsorbent composite may include an adsorbent filler that can be embedded within the matrix of the polymer material. In some embodiments, the polymer material 104 may include fibrils. In some embodiments, the polymer material 104 may be stretched PTFE.

[0089] In some embodiments, the adsorbent packing material may include activated carbon, silica, metal-organic structures, zeolites, alumina, alkali metal oxides, polymer adsorbents, alkali carbonates, ion exchange resins, polyethyleneimine (PEI), or combinations thereof. In some embodiments, the activated carbon may be obtained from coal, lignite, wood, coconut shells, other carbonaceous materials, or any combination thereof.

[0090] In some embodiments, the adsorbent filler may contain at least one amine group. In some embodiments, the adsorbent filler may include an impregnated amine, an amine supported on a polymer, an amine supported on a metal oxide, an amine supported on carbon, an amine-functionalized polymer, or any combination thereof.

[0091] In some embodiments, the adsorbent composite material may not contain a mineral binder. In some embodiments, the mineral binder may include minerals selected from the group including natural clay, bentonite, attapulgite, kaolin, alumina, silica, gypsum, and combinations thereof.

[0092] Microwave-transparent binders can be materials with low dielectric loss coefficients. Examples of such materials include polymers such as polystyrene, PTFE, and polyethylene.

[0093] In some embodiments, the microwave-transmissive binder can have a dielectric loss coefficient of 0.1 or less.

[0094] In some embodiments, the microwave-transparent binder can have a dielectric loss coefficient of about 0.0001-0.1, 0.002-0.1, 0.003-0.1, 0.004-0.1, 0.005-0.1, 0.006-0.1, 0.007-0.1, 0.008-0.1, or about 0.009-0.1.

[0095] In some embodiments, the microwave-transparent binder can have a dielectric loss coefficient of about 0.01-0.1, 0.015-0.1, 0.02-0.1, 0.025-0.1, 0.03-0.1, 0.035-0.1, 0.04-0.1, 0.045-0.1, 0.05-0.1, 0.055-0.1, 0.06-0.1, 0.065-0.1, 0.07-0.1, 0.075-0.1, 0.08-0.1, 0.085-0.1, 0.09-0.1, or about 0.095-0.1.

[0096] In some embodiments, the microwave-permeable binder has a viscosity of approximately 0.0025~0.05, 0.005~0.0525, 0.0075~0.055, 0.01~0.0575, 0.0125~0.06, 0.015~0.0625, 0.0175~0.065, 0.02~0.0675, 0.0225~0.07, 0.025~0.0725, The dielectric loss coefficient can be 0.0275~0.075, 0.03~0.0775, 0.0325~0.08, 0.035~0.0825, 0.0375~0.085, 0.04~0.0875, 0.0425~0.09, 0.045~0.0925, 0.0475~0.095, 0.05~0.0975, or 0.055~0.1.

[0097] In some embodiments, the microwave-transparent binder may have a reflectance coefficient of less than 0.5, 0.4, 0.3, 0.2, or 0.1. In some embodiments, the microwave-transparent binder may have a reflectance coefficient of about 0.15–0.45, 0.2–0.45, 0.25–0.45, 0.15–0.4, 0.2–0.4, 0.25–0.4, 0.15–0.35, 0.2–0.35, or 0.25–0.35.

[0098] In some embodiments, the microwave-transmitting binder may have a transmittance coefficient of at least 0.7, 0.8, or 0.9. In some embodiments, the microwave-transmitting binder may have a reflectance coefficient of about 0.7 to 1, 0.8 to 1, 0.9 to 1, 0.7 to 0.975, 0.8 to 0.975, 0.9 to 0.975, 0.7 to 0.95, 0.8 to 0.95, or 0.9 to 0.95.

[0099] In some embodiments, the microwave-permeable binder may include a polymer.

[0100] In some embodiments, the polymer may have a dielectric constant of about 0.5–5, 1–4.5, 1.5–4, 2–3.5, or 2.5–3. In some embodiments, the polymer may have a dielectric constant of about 0.5–4, 1–4, 1.5–4, 2–4, 2.5–4, 3–4, or 3.5–4.

[0101] In some embodiments, the polymer may include hydrocarbon polymers, fluoropolymers, polyolefins, or combinations thereof.

[0102] In some embodiments, the polyolefin can be selected from the group comprising polyethylene, polypropylene, ethylenepropylene diene terpolymer, and random copolymers containing at least one propylene group, at least one ethylene group, and at least one butene group and / or hexene group.

[0103] In some embodiments, the polymer is polybenzimidazole (PBI), polyamideimide (PAI), polyimide (PI), polyethersulfone (PES), fluorinated ethylene propylene (FEP), polyetherimide (PEI), polysulfone (PSU), polyamide (PA), cellulose, methylcellulose, cellulose ester, polystyrene (PS), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA or PVOH), polyvinyl butyral (PVB), polyvinyl chloride (PVC), polyvinylpyrrolidone (PVP), polyphenylene sulfide (PPS), polyf The compounds may include compounds selected from the group comprising polyethylenepropylene (PFEP), polyperfluoroacrylate (PPFA), polyvinylidene fluoride (PVDF), terpolymers of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride (THV), polychlorotrifluoroethylene (PCFE), poly(ethylene-co-tetrafluoroethylene) (ETFE), ultra-high molecular weight polyethylene (UHMWPE), polyparaxylylene (PPX), polylactic acid (PLLA), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), cyclic olefin polymers (COP), cyclic olefin copolymers (COC), their expanded derivatives, and combinations thereof.

[0104] In preferred embodiments, the polymer may include cellulose, polytetrafluoroethylene (PTFE), polyethylene, polypropylene, polyether ether ketone (PEEK), polyether ketone ketone (PEKK), their expanded derivatives, or combinations thereof. In some examples, expanded polymers, such as ePTFE, have pores, unlike unexpanded polymers (e.g., PTFE).

[0105] In some embodiments, the polymer has a density of 0.1 g / cm³ 3 ~2.2g / cm 3 It can be in the range of . In another example, the expanding polymer has a density of 0.5 g / cm³.3 ~2g / cm 3 , 1g / cm 3 ~1.5g / cm 3 , or 0.2g / cm 3 ~2g / cm 3 can be in the range of.

[0106] In preferred embodiments, the polymer can comprise expanded polytetrafluoroethylene (ePTFE), expanded polyethylene (ePE), expanded polypropylene (ePP), polyether ether ketone (PEEK), polyether ketone ketone (PEKK), and cellulose.

[0107] As one representative polymer example, the structure of PTFE is advantageous in that it becomes porous with micropores formed between polymer fibrils and nodes during stretching, depending on the stretching conditions under which the polymer material is used. When an adsorbent material such as an adsorbent filler is mixed with PTFE or a polymer having similar properties, the adsorbent filler can be embedded or entangled in various void structures of the polymer.

[0108] Figures 2A to 2C show the cross-sectional structures of various exemplary adsorbent composite sheets as resolved using a scanning electron microscope (SEM).

[0109] Figure 2A shows an exemplary structure of an adsorbent composite 200 comprising 3A zeolite powder and a microwave-permeable binder. For reference, 3A zeolite has the chemical formula K 12 "(AlO2) 12The material has (SiO2)·X H2O, with a silica-to-alumina ratio of approximately 2 and a pore size of approximately 3 Å. The sheet structure includes a raised surface 240 containing at least one raised portion 210 and a flat surface 220 facing it. In this non-limiting embodiment, the adsorbent composite has a base thickness of 1.83 mm, a sheet width of 280 mm, and a distance of 1490 μm between the two raised portions. The base thickness was measured from the bottom of the flat surface 220 to the top of the raised portion 230. The distance between the two raised portions was measured from the lowest point of one raised portion to the lowest point of the adjacent raised portion, e.g., the "valley distance". The amount of adsorbent filler, i.e., 3A zeolite, in the exemplary adsorbent composite is 85% wt / wt, and this should not be interpreted as limiting.

[0110] Figure 2B shows an exemplary structure of an adsorbent composite 200b containing 5A zeolite powder and a microwave-permeable binder. For reference, the chemical formula of 5A zeolite is 3 / 4Ca2O·1 / 4Na2O·Al2O3·2SiO2·9 / 2H2O, with a silica-alumina ratio of approximately 2 and a pore size of approximately 5 Å. In this non-limiting embodiment of the absorbent composite, the amount of adsorbent filler, i.e., 5A zeolite, was 85% wt / wt. The structure includes a raised surface 240b containing at least one raised portion 210b and a flat surface 220b facing it. In this non-limiting embodiment, the absorbent composite has a base thickness of 1.14 mm, a sheet width of 280 mm, and a distance of 1120 μm between the two raised portions. The base thickness was measured from the bottom of the flat surface 220b to the top of the raised portion 230b. The distance between two raised areas is measured from the lowest point of one raised area to the lowest point of the adjacent raised area, a distance of 260b, and is, for example, the "valley distance." The amount of adsorbent filler, i.e., 5A zeolite, in the exemplary adsorbent composite material is 85% wt / wt, and this should not be interpreted as limiting.

[0111] Figure 2C shows an exemplary structure of an adsorbent composite 200c containing silica and a microwave-permeable binder. This structure has a flat surface 220c opposite a raised surface 240c which includes at least one raised portion 210c. In this non-limiting embodiment, the adsorbent composite has a base thickness of 1.96 mm, a sheet width of 280 mm, and a distance of 1490 μm between the two raised portions. The base thickness was measured from the bottom of the flat surface 220c to the top of the raised portion 230c. The distance between the two raised portions was measured from the lowest point of one raised portion to the lowest point of the adjacent raised portion, 260c, which is, for example, the "valley distance". The amount of adsorbent filler, i.e., silica, in the exemplary adsorbent composite is 85% wt / wt, and this should not be interpreted as limiting.

[0112] These exemplary structures, including those containing multiple layers of sheets having the same structure, and those containing multiple raised sections with opposing flat surfaces, function as parallel-passage contactors through which a gas flow can pass. From this given structure, various orientations are possible, such as sheets stacked with raised sections facing each other, flat surfaces facing each other, raised sections with flat surfaces, or combinations thereof, and sheets wound spirally in a circular shape with the apex of the raised sections facing the center of the circle, the outer edge of the circle, or a combination thereof.

[0113] Figure 3 shows a cross-sectional structure of an exemplary adsorbent composite 300, including 13X zeolite and a microwave-transparent binder, as resolved using a SEM. The adsorbent composite 300 has a plurality of repeating quadrilateral units, such as rhombic or diamond shapes 320, each unit having a hollow cavity 340. The vertices 310 of rhombic shapes directly opposite each other are separated by defined spaces extending horizontally and vertically, thereby forming the hollow cavity 340. Furthermore, the vertices of adjacent rhombic shapes are in direct contact without a space between them 350. In this non-limiting embodiment, the adsorbent composite has a vertex thickness of 1.83 mm, a sheet width of 50 mm, and a spacing of 484 μm between adjacent ridges. The vertex thickness was measured as the maximum distance between two directly opposite vertices. For reference, the chemical formula of 13X zeolite powder is Na2O·Al2O3·(2.8±0.2)SiO2·(6-7)H2O, with a silica-to-alumina ratio of approximately 2.6-3.0 and a pore size of approximately 9 Å. In this non-limiting embodiment, the adsorbent composite may contain an adsorbent filler, i.e., 13X zeolite, at 65% wt / wt. This exemplary structure, including a sheet in which sheets having the same structure are arranged in multiple overlapping layers, functions as a parallel-passage contactor through which a gas flow can pass.

[0114] In some embodiments, the adsorbent composite may include a parallel-passage contactor structure. In some embodiments, the adsorbent composite may include one or more self-supporting adsorbent sheets. In some embodiments, "self-supporting" means that the sheets do not require a support layer or backing. In some embodiments, the adsorbent composite may include substantially parallel raised portions arranged on one or more self-supporting adsorbent sheets.

[0115] In some embodiments, the sheet may include a first surface and a second surface opposite to the first surface. In some embodiments, the first surface is configured such that when a gas stream (e.g., a flue gas stream, but not limited to CO2) having at least one gaseous component flows over (and passes through) the first surface of at least one sheet, at least one gaseous component is adsorbed onto an adsorbent material such as an adsorbent filler of an adsorbent composite. In some embodiments, at least one gaseous component may flow over (and pass through) both the first surface and the second surface of at least one sheet.

[0116] In some embodiments, one or more self-supporting adsorbent sheets are arranged as a plurality of overlapping layers. In some embodiments, the plurality of overlapping layers are spaced apart by substantially parallel ridges to allow gas to flow between the layers. In some embodiments, the ridges may be formed by embossing, engraving, molding, or stamping.

[0117] In some embodiments, the adsorbent sheets are arranged horizontally, vertically, and diagonally. In some embodiments, the sheets are wound spirally. In some embodiments, the sheets are folded into a quadrilateral shape, such as a square or rectangle. In some embodiments, at least two sheets are shaped with at least three sides, such as a polygon. In some embodiments, the polygon is a triangle, quadrilateral, pentagon, hexagon, heptagon, octagon, nonagon, or decagon. In some embodiments, at least two sheets are shaped with at least three sides, of which at least one side is curved. In some embodiments, at least two sheets are stacked.

[0118] Figure 4 shows a top view of a sheet of an adsorbent composite material arranged in a helical orientation 400. The overlapping layers 420 are spaced apart by hollow repeating rectangular units 440, for example, forming voids 460 to create a parallel-passage contactor structure, which allows gas to flow between the multiple voids 460 and layers 420.

[0119] In some embodiments, the sheet of the adsorbent composite material can have a thickness of approximately 0.01-3 mm, 0.02-3 mm, 0.03-3 mm, 0.04-3 mm, 0.05-3 mm, 0.06-3 mm, 0.07-3 mm, 0.08-3 mm, 0.09-3 mm, 0.1-3 mm, 0.15-3 mm, 0.2-3 mm, 0.25-3 mm, 0.3-3 mm, 0.35-3 mm, 0.4-3 mm, 0.45-3 mm, or 0.5-3 mm.

[0120] In some embodiments, the sheet of the adsorbent composite material can have a thickness of approximately 0.01-1 mm, 0.02-1 mm, 0.03-1 mm, 0.04-1 mm, 0.05-1 mm, 0.06-1 mm, 0.07-1 mm, 0.08-1 mm, 0.09-1 mm, 0.1-1 mm, 0.15-1 mm, 0.2-1 mm, 0.25-1 mm, 0.3-1 mm, 0.35-1 mm, 0.4-1 mm, 0.45-1 mm, or 0.5-1 mm.

[0121] In some embodiments, the sheet of the adsorbent composite material can have a thickness of approximately 0.1-10 mm, 0.5-9.5 mm, 1-9 mm, 1.5-8.5 mm, 2-8 mm, 2.5-7.5 mm, 3-7 mm, 3.5-6.5 mm, 4-6 mm, 4.5-5.5 mm, 0.2 mm-2 mm, 0.4 mm-2 mm, 0.5 mm-2 mm, 0.5 mm-1.75 mm, or 0.5 mm-1.5 mm.

[0122] In some embodiments, the sheet of the adsorbent composite material can have a thickness of approximately 0.2mm to 2mm, 0.3mm to 2mm, 0.4mm to 2mm, 0.5mm to 2mm, 0.6mm to 2mm, 0.7mm to 2mm, 0.8mm to 2mm, 0.8mm to 2mm, 0.9mm to 2mm, 1mm to 2mm, 1.1mm to 2mm, 1.2mm to 2mm, 1.3mm to 2mm, 1.4mm to 2mm, 1.5mm to 2mm, 1.6mm to 2mm, 1.7mm to 2mm, 1.8mm to 2mm, or 1.9mm to 2mm.

[0123] In some embodiments, the sheet of the adsorbent composite material can have a thickness of approximately 0.2 mm to 1.75 mm, 0.3 mm to 1.6 mm, 0.4 mm to 1.6 mm, 0.5 mm to 1.55 mm, or 0.5 mm to 1.5 mm.

[0124] In some cases, the thickness of an adsorbent composite can be measured using a cross-sectional scanning electron microscope. In some cases, the thickness of a sheet can be measured, as described herein, by measuring the distance from the largest distance between one face of the sheet to the opposite face of the sheet, for example, the distance from the bottom of a flat surface to the top of a raised surface, for example, the thickness from top to bottom, or by measuring the maximum distance between one top and another directly opposite top, for example, the thickness between tops. In other cases, for example, considering a raised adsorbent composite such as a sheet having a raised surface opposite a flat surface, the thickness can be measured from the base of the raised surface to the bottom of the flat surface, for example, the thickness from the base of the raised surface to the bottom.

[0125] In some embodiments, the sheet of the raised-adsorbent composite material may have a ratio of thickness from top to bottom to thickness from base to bottom of the raised area of ​​about 10:1 to 1:10, 8:1 to 1:8, 6:1 to 1:6, 4:1 to 1:4, or 2:1 to 1:2. In some embodiments, the sheet of the raised-adsorbent composite material may have a ratio of thickness from top to bottom to thickness from base to bottom of the raised area of ​​about 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, or 1:5. In some embodiments, the sheet of the raised-adsorbent composite material may have a ratio of thickness from top to bottom to thickness from base to bottom of the raised area of ​​about 5:4, 5:3, 5:2, 4:3, 3:2, 2:3, 3:4, 2:5, 3:5, or 4:5. In some embodiments, the raised-adhesion composite material includes a plurality of convex protrusions. In some embodiments, the raised-adhesion composite material includes a plurality of concave protrusions. In some embodiments, the raised-adhesion composite material includes a combination of convex and concave protrusions.

[0126] In some embodiments, the sheet of the adsorbent composite material can have a width of approximately 10-1500 mm, 20-1250 mm, 30-1000 mm, 40-750 mm, 50-500 mm, or 60-250 mm.

[0127] In some embodiments, the sheet of the adsorbent composite material can have a width of approximately 25-2500 mm, 50-2000 mm, 100-1750 mm, 150-1500 mm, 200-1250 mm, 250-1000 mm, 300-750 mm, or 350-500 mm.

[0128] In some embodiments, the sheet of the adsorbent composite material can have a width of approximately 25-500 mm, 50-500 mm, 100-500 mm, 150-500 mm, 200-500 mm, 250-500 mm, 300-500 mm, or 350-500 mm.

[0129] In some embodiments, the sheet of the adsorbent composite material can have a width of approximately 25-250 mm, 50-250 mm, 100-250 mm, 150-250 mm, 200-250 mm, 10-100 mm, 20-100 mm, 30-100 mm, 40-100 mm, 50-100 mm, 60-100 mm, 70-100 mm, 80-100 mm, or 90-100 mm. In some embodiments, the width of the adsorbent composite material can be measured using a cross-sectional scanning electron microscope.

[0130] In some embodiments, the adsorbent composite material may include at least one raised portion. In some embodiments, the adsorbent composite material may include a plurality of raised portions.

[0131] In some embodiments, the spacing between adjacent raised portions is 5 μm, 15 μm, 75 μm, 150 μm, 250 μm, 500 μm, 750 μm, 1000 μm, 1250 μm, 1500 μm, 1750 μm, 2000 μm, 2250 μm, 2500 μm, 2750 μm, 3000 μm, 3250 μm, 3500 μm, 3750 μm, 4000 μm, 4250 μm, 4500 μm The thickness can be 4750μm, 5000μm, 5250μm, 5500μm, 5750μm, 6000μm, 6250μm, 6500μm, 6750μm, 7000μm, 7250μm, 7500μm, 7750μm, 8000μm, 8250μm, 8500μm, 8750μm, 9000μm, 9250μm, 9500μm, 9750μm, or 10000μm or less.

[0132] In some embodiments, the spacing between adjacent raised areas is approximately 200-2000 μm, 250-2000 μm, 300-2000 μm, 350-2000 μm, 400-2000 μm, 450-2000 μm, 500-2000 μm, 550-2000 μm, 600-2000 μm, 650-2000 μm, 700-2000 μm, 750-2000 μm, 800-2000 μm, 850-2000 μm, 900-2000 μm, 950-2000 μm, 1000-2000 μm, and 1050-2000 μm. The particle size can be 1100-2000 μm, 1150-2000 μm, 1200-2000 μm, 1250-2000 μm, 1300-2000 μm, 1350-2000 μm, 1400-2000 μm, 1450-2000 μm, 1500-2000 μm, 1550-2000 μm, 1600-2000 μm, 1650-2000 μm, 1700-2000 μm, 1750-2000 μm, 1800-2000 μm, 1850-2000 μm, 1900-2000 μm, or 1950-2000 μm.

[0133] In some embodiments, the spacing between adjacent raised areas is approximately 5 μm to 10,000 μm, 15 μm to 10,000 μm, 150 μm to 10,000 μm, 250 μm to 10,000 μm, 500 μm to 10,000 μm, 750 μm to 10,000 μm, 1,000 μm to 10,000 μm, 1250 μm to 10,000 μm, 1,500 μm to 10,000 μm, 1,750 μm to 10000μm, 2000μm~10000μm, 2250μm~10000μm, 2500μm~10000μm, 2750μm~10 000μm, 3000μm~10000μm, 3250μm~10000μm, 3500μm~10000μm, 3750μm~1000 0μm, 4000μm~10000μm, 4250μm~10000μm, 4500μm~10000μm, 4750μm~10000μm m, 5000μm~10000μm, 5250μm~10000μm, 5500μm~10000μm, 5750μm~10000μm, 6 The particle size can be 000μm~10000μm, 6250μm~10000μm, 6500μm~10000μm, 6750μm~10000μm, 7000μm~10000μm, 7250μm~10000μm, 7500μm~10000μm, 7750μm~10000μm, 8000μm~10000μm, 8250μm~10000μm, 8500μm~10000μm, 8750μm~10000μm, 9000μm~10000μm, 9250μm~10000μm, 9500μm~10000μm, or 9750μm~10000μm.

[0134] In some embodiments, the distance between the ridges can be uniform throughout the structure of the adsorbent composite. In some embodiments, the distance between the ridges can be non-uniform or vary throughout the structure of the adsorbent composite. In a preferred embodiment, the distance between two adjacent ridges can be measured as the distance from the lowest point of one ridge to the lowest point of the adjacent ridge, for example, as the valley distance.

[0135] Figure 5A shows a non-limiting embodiment of an adsorbent composite material comprising an adsorbent packing material and a microwave-permeable binder within an adsorption column as described herein, for example, to promote the shrinkage of a uniform parallel passage. In some embodiments, the adsorption column is made from aluminum, steel, stainless steel, polyurethane, polyethylene, polypropylene, polyetherimide, PFA, FEP, PTFE, or vinyl ethyl acetate (EVA). The diameter of the column can be from 0.001 m to 20 m. In some embodiments, the adsorbent composite material is housed in a heat-shrink tubing.

[0136] On the other hand, Figure 5B shows an adsorbent containing beads such as zeolite beads in a comparative example.

[0137] A bead-packed bed refers to a container densely packed with multiple spherical particles, such as solid spherical particles. When gas passes through such a packed bed, it encounters a complex and irregular network of gaps between the beads, which can result in a meandering gas flow path. Such a gas flow path can lead to non-uniformity of the flow rate distribution. On the other hand, a parallel-passage contactor is a structure designed to control or direct the flow of gas through a series of parallel passages. In one example, considering an exemplary embodiment with repeating hollow rhomboid cross-sections, such a structure promotes controlled contraction of the gas flow. The symmetrical and regular arrangement promotes uniformity of the gas flow, and the gas flow passing through each passage undergoes the same degree of contraction. Furthermore, the controlled contraction of the gas flow in a parallel-passage contactor can reduce the pressure drop compared to a bead-packed bed because the flow path becomes streamlined, and it is possible to adjust the passage size to change gradually.

[0138] In some embodiments, the adsorbent composite material may include a microwave-permeable binder. In some embodiments, the microwave-permeable binder may include a microstructure consisting of fibrils or fibrils and nodes. In some embodiments, the microstructure of the microwave-permeable binder may have void volumes.

[0139] In some embodiments, the adsorbent composite material may include an adsorbent, such as an adsorbent filler. In some embodiments, the adsorbent filler is partially or completely embedded in at least a portion of the microstructure of the microwave-permeable binder, in the spaces between layers of a multilayer microwave-permeable binder, in the void volume of the microwave-permeable binder, or a combination thereof.

[0140] In some embodiments, the adsorbent composite may contain adsorbent fillers in amounts of approximately 5% to 99% (w / w), 10% to 95% (w / w), 15% to 90% (w / w), 20% to 85% (w / w), 25% to 80% (w / w), 30% to 75% (w / w), 35% to 70% (w / w), 40% to 65% (w / w), 45% to 60% (w / w), or 50% to 55% (w / w), based on the total weight of the adsorbent composite.

[0141] In some embodiments, the adsorbent composite material may have a total porosity of approximately 10% to 95%, 20% to 95%, 30% to 95%, 40% to 95%, 50% to 95%, 60% to 95%, 70% to 95%, 80% to 95%, or 90% to 95%.

[0142] In some embodiments, the adsorbent composite material may have a total porosity of approximately 25% to 95%, 30% to 90%, 35% to 85%, 40% to 80%, 45% to 75%, 50% to 70%, or 55% to 65%.

[0143] In some embodiments, the adsorbent composite material may include an adsorbent filler comprising a high-loss dielectric material, a low-loss dielectric material, or a combination thereof.

[0144] In some embodiments, the high-loss dielectric material may have a loss tangent of at least 0.1. In some embodiments, the high-loss dielectric material may have a loss tangent of about 0.1 to 1.0, 0.2 to 0.9, 0.3 to 0.8, 0.4 to 0.7, or 0.5 to 0.6. In some embodiments, the high-loss dielectric material may have a loss tangent of about 0.1 to 1.0, 0.2 to 1.0, 0.3 to 1.0, 0.4 to 1.0, 0.5 to 1.0, 0.6 to 1.0, 0.7 to 1.0, 0.8 to 1.0, or 0.9 to 1.0.

[0145] In some embodiments, low-loss dielectric materials can have a loss tangent of about 0.1, 0.09, 0.08, 0.07, 0.06, or less than 0.05. In some embodiments, low-loss dielectric materials can have a loss tangent of about 0.001-0.1, 0.002-0.09, 0.003-0.08, 0.004-0.07, 0.005-0.06, 0.006-0.05, 0.007-0.04, 0.008-0.03, 0.009-0.02. In some embodiments, low-loss dielectric materials can have a loss tangent of about 0.01-0.1, 0.02-0.09, 0.03-0.07, 0.04-0.06, 0.05-0.55.

[0146] In some embodiments, the adsorbent composite may include at least about 75%, 80%, 85%, 90%, or 95% of an adsorbent material, such as an adsorbent filler, and the remainder of a microwave-permeable binder.

[0147] In some embodiments, the adsorbent composite may include approximately 5% to 95%, 10% to 90%, 15% to 85%, 20% to 80%, 25% to 75%, 30% to 70%, 35% to 65%, 40% to 60%, 45% to 55%, 60% to 95%, 65% to 90%, 70% to 85%, or 75% to 80% of an adsorbent material, such as an adsorbent filler, and the remainder being a microwave-permeable binder.

[0148] In some embodiments, the adsorbent composite may include approximately 5% to 95%, 10% to 90%, 15% to 85%, 20% to 80%, 25% to 75%, 30% to 70%, 35% to 65%, 40% to 60%, or 45% to 55% of a microwave-permeable binder and adsorbent material such as the remaining adsorbent filler.

[0149] In some embodiments, the adsorbent composite may include approximately 1%-20%, 5%-20%, 10%-20%, 15%-20%, 1%-15%, 5%-15%, 10%-15%, 1%-10%, or 5%-10% of a microwave-permeable binder and adsorbent material such as the remaining adsorbent filler.

[0150] In some embodiments, the adsorbent composite material contains adsorbent materials such as activated carbon, silica, metal-organic structures, zeolites, alumina, alkali metal oxides, polymer adsorbents, alkali carbonates, ion exchange resins, polyethyleneimine (PEI), impregnated amines, amines supported on polymers, amines supported on metal oxides, amines supported on carbon, amine-functionalized polymers, or combinations thereof, in total amounts of about 5% to 95%, 10% to 90%, 15% to 85%, 20% to 80%, 25% to 75%, 30% to 70%, 35% to 65%, 40% to 60%, 45% to 55%, 60% to 95%, 65% to 90%, 70% to 85%, or 75% to 80%, with the remainder being a microwave-permeable binder containing hydrocarbon polymers, fluoropolymers, polyolefins, or combinations thereof.

[0151] In some embodiments, the adsorbent composite material contains a total of about 5% to 95%, 10% to 90%, 15% to 85%, 20% to 80%, 25% to 75%, 30% to 70%, 35% to 65%, 40% to 60%, or 45% to 55% of a microwave-permeable binder comprising hydrocarbon polymers, fluoropolymers, polyolefins, or combinations thereof, and the remainder may be an adsorbent filler material such as activated carbon, silica, metal-organic structures, zeolites, alumina, alkali metal oxides, polymer adsorbents, alkali carbonates, ion exchange resins, polyethyleneimines, impregnated amines, amines supported on polymers, amines supported on metal oxides, amines supported on carbon, amine-functionalized polymers, or combinations thereof.

[0152] In some embodiments, the adsorbent composite may comprise an adsorbent filler containing approximately 5% to 95%, 10% to 90%, 15% to 85%, 20% to 80%, 25% to 75%, 30% to 70%, 35% to 65%, 40% to 60%, 45% to 55%, 60% to 95%, 65% to 90%, 70% to 85%, or 75% to 80% of an adsorbent material, such as zeolite and / or silica, with the remainder being a microwave-permeable binder containing PTFE.

[0153] In a preferred embodiment, the adsorbent composite material contains a microwave-permeable binder containing PTFE in amounts of about 1% to 20%, 5% to 20%, 10% to 20%, 15% to 20%, 1% to 15%, 5% to 15%, 10% to 15%, 1% to 10%, or 5% to 10%, with the remainder being an adsorbent material such as an adsorbent filler containing zeolite and / or silica.

[0154] Figure 6 shows a non-limiting embodiment of a system for adsorbing and desorbing adsorbate 600 from a gas flow or the like, the system comprising an inlet opening 620, an adsorption unit 640 including an adsorbent composite 660, a microwave unit 680 housing the adsorption unit 640, and an outlet opening 690. The adsorbate, for example, a gas flow or saturated humidity, enters the system through the inlet opening 620 and is adsorbed onto the adsorbent composite 660 housed in the adsorption unit 640. In one embodiment, the adsorbate is present in a gas flow such as a fluid flow. In another embodiment, the adsorbate is water introduced into the system by the passage of water vapor through the inlet opening. In some embodiments, the water is adsorbed onto the adsorbent composite and then desorbed from the adsorbent composite before a gas flow flows in through the inlet opening and subsequently adsorbs the adsorbate of the gas flow. The adsorption unit 640, which contains the adsorbent composite material 660, is located within a microwave unit 680 used to expose the adsorption unit 640 to microwave irradiation, thereby promoting the desorption of the adsorbent from the adsorbent composite material 660. The desorbed adsorbate is then discharged from the system through an outlet opening 690 and can be recovered for analysis, such as determining the desorption efficiency.

[0155] Figure 7 shows non-limiting embodiments of the adsorption unit 700. In some embodiments, the adsorption unit 700 houses a total of one adsorption column 720, such as an adsorption column containing an adsorbent composite material 730 as described herein. In some embodiments, the adsorption unit 700 houses multiple adsorption columns. In some embodiments, the adsorption unit 700 may have at least one fluid inlet 740 and at least one fluid outlet 760. In one example, a cooling fluid, such as a cooling gas, coolant, or a combination thereof, can be introduced into the adsorption unit through the fluid inlet 740 to promote cooling or control the temperature during the adsorption process. The fluid can be discharged from the adsorption unit through the fluid outlet 760. In another example, a high-temperature fluid, such as steam, can be introduced into the adsorption unit 700 to promote heating. In some embodiments, the cooling fluid and / or high-temperature fluid can be in contact with the outside of the column.

[0156] In some embodiments, the adsorption unit may have at least one fluid inlet 770 for introducing a fluid flow into the adsorption unit 700 and at least one fluid outlet 780 for discharging the fluid flow from the adsorption unit 700. In some embodiments, at least a portion of the fluid introduced into the adsorption unit 700 passes through an adsorption column 720, such as an adsorption column containing an adsorbent composite material 730 as described herein. In some embodiments, the fluid flow includes at least one gas, at least one liquid, or a combination thereof. In some embodiments, the fluid flow includes an adsorbate.

[0157] In some embodiments, the adsorption unit 700 houses an array of adsorption columns 750, such as a plurality of columns arranged in a systematic orientation. In some embodiments, the adsorption columns 720 may be arranged vertically, horizontally, or obliquely within the adsorption unit 700. In some embodiments, in an adsorption unit 700 housing a plurality of adsorption columns 720, each adsorption column may be oriented in the same direction, for example, each of the plurality of adsorption columns may be arranged horizontally in a plane. In some embodiments, in an adsorption unit 700 housing a plurality of adsorption columns 720, the plurality of adsorption columns may be oriented in distinct directions, for example, some columns may be arranged vertically in a plane and others horizontally. In some embodiments, the adsorption unit 700 may be arranged vertically, horizontally, or obliquely in a plane.

[0158] In some embodiments, multiple adsorption units may be stacked, for example, in a multi-layer arrangement. In some embodiments, a fluid, such as a cooling fluid and / or a temperature control fluid such as a heating fluid, can be introduced into the space between layers from a fluid inlet to promote cooling and heating.

[0159] In some embodiments, the array of adsorption columns 750 may have a shell-and-tube structure. In one example, a fluid flow containing a gas mixture containing adsorbate enters the “shell” and flows through the “tube”. In some examples, the shell is an outer housing or container that houses the array of adsorption columns 750. In some examples, the tubes in the shell-and-tube arrangement may be adsorption columns 720, such as adsorption columns containing the adsorbent composite material 730 as described herein. The shell may be cylindrical, rectangular, or any other shape designed to withstand pressure and temperature fluctuations in a temperature swing adsorption process.

[0160] In some embodiments, the array of adsorption columns 750 may have a laminated sheet orientation. In one example, the laminated sheet orientation may include multiple sheets in a laminated orientation such as a layered orientation. In some examples, the sheets are arranged parallel and close together, thereby forming narrow channels or passages between the sheets.

[0161] Other embodiments of the present disclosure relate to a method that includes using an adsorbent composite material to separate gaseous components from a gas mixture in a temperature swing adsorption process.

[0162] In some embodiments, the present disclosure relates to a method for desorbing an adsorbent, such as an adsorbate from a gas flow, from an adsorption unit comprising an adsorbent composite material as described herein. This desorption method includes irradiating an adsorption unit on which the adsorbent is adsorbed with an adsorbent composite material with electromagnetic waves, wherein the irradiation promotes the desorption of the adsorbent from the adsorbent composite material.

[0163] In some embodiments, the fluid flow may include an adsorbent. In some embodiments, the fluid flow may include a fluid gas flow. In some embodiments, the fluid flow may include water vapor. In some embodiments, the adsorbent may be hydrogen gas (H2), methane (CH4), carbon monoxide (CO), carbon dioxide (CO2), water (H2O), nitrogen oxides (NO2). x), sulfur oxides (SO x ), volatile organic compounds (VOCs), or combinations thereof, or may include them.

[0164] In some embodiments, the fluid flow may contain a single compound, such as a single adsorbate, at concentrations of at least 10 ppb (0.01 ppm), 50 ppb (0.5 ppm), 100 ppb (0.1 ppm), 200 ppb (0.2 ppm), 300 ppb (0.3 ppm), 400 ppb (0.4 ppm), 500 ppb (0.5 ppm), 600 ppb (0.6 ppm), 700 ppb (0.7 ppm), 800 ppb (0.8 ppm), 900 ppb (0.9 ppm), and 1000 ppb (1 ppm).

[0165] In some embodiments, the fluid flow may contain a single compound, such as a single adsorbate, at a concentration of at least 1 ppm, 100,000 ppm, 200,000 ppm, 300,000 ppm, 400,000 ppm, 500,000 ppm, 600,000 ppm, 700,000 ppm, 800,000 ppm, or 900,000 ppm.

[0166] In some embodiments, the fluid flow may contain a single compound, such as a single adsorbate, at a concentration of approximately 10 ppm, 100 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm, 10000 ppm, 11000 ppm, 12000 ppm, 13000 ppm, 14000 ppm, 15000 ppm, 16000 ppm, 17000 ppm, 18000 ppm, 19000 ppm, 20000 ppm, 21000 ppm, 22000 ppm, 23000 ppm, 24000 ppm, or 25000 ppm or less.

[0167] In some embodiments, the fluid stream may contain a single compound, such as a single adsorbate, at concentrations of about 30,000 ppm, 35,000 ppm, 40,000 ppm, 45,000 ppm, 50,000 ppm, 55,000 ppm, 60,000 ppm, 65,000 ppm, 70,000 ppm, 75,000 ppm, 80,000 ppm, 85,000 ppm, 90,000 ppm, 95,000 ppm, or 100,000 ppm or less.

[0168] In some embodiments, the fluid flow may contain a single compound, such as a single adsorbate, at concentrations of approximately 150,000 ppm, 200,000 ppm, 300,000 ppm, 400,000 ppm, 500,000 ppm, 600,000 ppm, 700,000 ppm, 800,000 ppm, 900,000 ppm, or 999,900 ppm or less.

[0169] In some embodiments, the fluid flow may contain a single compound, such as a single adsorbate, at concentrations of approximately 0.01 ppb to 5000 ppb, 0.1 ppb to 5000 ppb, 1 ppb to 5000 ppb, 10 ppb to 5000 ppb, 100 ppb to 5000 ppb, 1000 ppb to 5000 ppb, 2000 ppb to 5000 ppb, 3000 ppb to 5000 ppb, or 4000 ppb to 5000 ppb.

[0170] In some embodiments, the fluid flow may contain a single compound, such as a single adsorbate, at concentrations of approximately 0.01 ppm to 5000 ppm, 0.1 ppm to 5000 ppm, 1 ppm to 5000 ppm, 10 ppm to 5000 ppm, 100 ppm to 5000 ppm, 1000 ppm to 5000 ppm, 2000 ppm to 5000 ppm, 3000 ppm to 5000 ppm, or 4000 ppm to 5000 ppm.

[0171] In some embodiments, the fluid flow dissolves a single compound, such as a single adsorbate, in concentrations of approximately 0 ppm to 990,000 ppm, 50,000 ppm to 990,000 ppm, 100,000 ppm to 990,000 ppm, 150,000 ppm to 990,000 ppm, 200,000 ppm to 990,000 ppm, 250,000 ppm to 990,000 ppm, 300,000 ppm to 990,000 ppm, 350,000 ppm to 990,000 ppm, 400,000 ppm to 990,000 ppm, and 450,000 ppm to 9 It can be included at concentrations of 90,000 ppm, 500,000 ppm to 990,000 ppm, 550,000 ppm to 990,000 ppm, 600,000 ppm to 990,000 ppm, 650,000 ppm to 990,000 ppm, 700,000 ppm to 990,000 ppm, 750,000 ppm to 990,000 ppm, 800,000 ppm to 990,000 ppm, 850,000 ppm to 990,000 ppm, 900,000 ppm to 990,000 ppm, or 950,000 ppm to 990,000 ppm.

[0172] In some embodiments, the fluid flow temperature can be at least -50°C, -40°C, -30°C, -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, or 70°C. In some embodiments, the fluid flow temperature can be 80°C or less.

[0173] In some embodiments, the fluid flow temperature can be -50°C to 80°C, -40°C to 80°C, -30°C to 80°C, -20°C to 80°C, -10°C to 80°C, 0°C to 80°C, 10°C to 80°C, 20°C to 80°C, 30°C to 80°C, 40°C to 80°C, 50°C to 80°C, 60°C to 80°C, or 70°C to 80°C. In some embodiments, the fluid flow temperature can be -50°C to 50°C, -40°C to 40°C, -30°C to 30°C, -20°C to 20°C, or 10°C to 10°C.

[0174] In some embodiments, the temperature of the fluid flow can be -50°C to 50°C, -40°C to 50°C, -30°C to 50°C, -20°C to 50°C, -10°C to 50°C, 0°C to 50°C, 10°C to 50°C, 20°C to 50°C, 30°C to 50°C, or 40°C to 50°C. In some embodiments, the temperature of the fluid flow can be -50°C to 25°C, -40°C to 25°C, -30°C to 25°C, -20°C to 25°C, -10°C to 25°C, 0°C to 25°C, 10°C to 25°C, or 20°C to 25°C.

[0175] In some embodiments, the pressure of the fluid flow can be reduced upon contact with the adsorbent composite material to approximately 0.5 kPa or less per meter of adsorbent composite material when the surface velocity is 0.2 meters per second or less, to 2 kPa or less per meter of adsorbent composite material when the surface velocity is 0.5 meters per second or less, or to 5 kPa or less per meter of adsorbent composite material when the surface velocity is 2 meters per second or less.

[0176] In some embodiments, the pressure of the fluid flow may decrease upon contact with the adsorbent composite by approximately 0.05 to 5 kPa per meter of the adsorbent composite, 0.15 to 5 kPa per meter of the adsorbent composite, 0.25 to 5 kPa per meter of the adsorbent composite, 0.35 to 5 kPa per meter of the adsorbent composite, 0.45 to 5 kPa per meter of the adsorbent composite, 0.55 to 5 kPa per meter of the adsorbent composite, 0.65 to 5 kPa per meter of the adsorbent composite, 0.75 to 5 kPa per meter of the adsorbent composite, 0.85 to 5 kPa per meter of the adsorbent composite, 1 to 5 kPa per meter of the adsorbent composite, 2 to 5 kPa per meter of the adsorbent composite, 3 to 5 kPa per meter of the adsorbent composite, or 4 to 5 kPa per meter of the adsorbent composite.

[0177] In some embodiments, the surface velocity of the fluid flow can be 1 meter per second, 1.5 meters per second, 2 meters per second, 2.5 meters per second, 3 meters per second, 3.5 meters per second, 4 meters per second, 4.5 meters per second, 5 meters per second, 5.5 meters per second, 6 meters per second, 6.5 meters per second, 7 meters per second, 7.5 meters per second, 8 meters per second, 8.5 meters per second, 9 meters per second, 9.5 meters per second, or 10 meters per second or less.

[0178] In some embodiments, the surface velocity of the fluid flow can be about 0.1–10 meters per second, 1–10 meters per second, 2–10 meters per second, 3–10 meters per second, 4–10 meters per second, 5–10 meters per second, 6–10 meters per second, 7–10 meters per second, 8–10 meters per second, or 9–10 meters per second.

[0179] In some embodiments, the surface velocity of the fluid flow can be about 0.1–2 meters per second, 0.2–2 meters per second, 0.3–2 meters per second, 0.4–2 meters per second, 0.5–2 meters per second, 0.6–2 meters per second, 0.7–2 meters per second, 0.8–2 meters per second, 0.9–2 meters per second, 1–2 meters per second, 1.1–2 meters per second, 1.2–2 meters per second, 1.3–2 meters per second, 1.4–2 meters per second, 1.5–2 meters per second, 1.6–2 meters per second, 1.7–2 meters per second, 1.8–2 meters per second, or 1.9–2 meters per second.

[0180] In some embodiments, the surface velocity of the fluid flow can be about 0.1 to 1 meter per second, 0.2 to 1 meter per second, 0.3 to 1 meter per second, 0.4 to 1 meter per second, 0.5 to 1 meter per second, 0.6 to 1 meter per second, 0.7 to 1 meter per second, 0.8 to 1 meter per second, or 0.9 to 1 meter per second.

[0181] In some embodiments, the fluid flow can have a relative humidity of 100% or less.

[0182] In some embodiments, the fluid flow can have a dew point of at least -120°C, -100°C, -80°C, -60°C, -40°C, -20°C, 0°C, 20°C, or 40°C.

[0183] In some embodiments, the fluid flow can have a dew point of approximately -120°C to 40°C, -100°C to 35°C, -80°C to 30°C, -60°C to 25°C, -40°C to 20°C, -20°C to 15°C, or 0°C to 10°C.

[0184] In some embodiments, the microwave unit includes microwaves, and the microwaves are transmitted to an adsorption unit including an adsorption composite material at 300 MHz (3 × 10⁻¹⁰ MHz). 8 Hz, λ=1m) ~ 300GHz (3 × 10⁻¹⁰ 11 Electromagnetic waves in the frequency range of Hz (λ=1mm) are irradiated.

[0185] In some embodiments, the microwave unit includes microwaves, which irradiate an adsorption unit containing an adsorption composite material with electromagnetic waves in the frequency range of 500 MHz to 50 GHz, 1 GHz to 100 GHz, 50 GHz to 150 GHz, 100 GHz to 200 GHz, 150 GHz to 250 GHz, or 200 GHz to 300 GHz.

[0186] In some embodiments, the microwave unit includes microwaves, which are irradiated onto an adsorption unit containing an adsorbent composite material in the frequency range of approximately 0.5 GHz to 3 GHz, 1 GHz to 3 GHz, 1.5 GHz to 3 GHz, 2 GHz to 3 GHz, or 2.5 GHz to 3 GHz.

[0187] In some embodiments, a microwave unit, such as a microwave generating unit, irradiates an adsorption unit containing an adsorbent composite material with microwaves in the frequency range of approximately 0.5 GHz to 2.5 GHz, 1 GHz to 2.5 GHz, 1.5 GHz to 2.5 GHz, or 2 GHz to 2.5 GHz.

[0188] In some embodiments, the output power of the microwave unit can be approximately 10Wt-100kW, 50Wt-100kW, 100Wt-100kW, 150Wt-100kW, 200Wt-100kW, 250Wt-100kW, 300Wt-100kW, 350Wt-100kW, 400Wt-100kW, 450Wt-100kW, 500Wt-100kW, 550Wt-100kW, 600Wt-100kW, 650Wt-100kW, 700Wt-100kW, 750Wt-100kW, 800Wt-100kW, 850Wt-100kW, 900Wt-100kW, 950Wt-100kW, or 1kW-100kW.

[0189] In some embodiments, the output power of the microwave unit can be approximately 10kW to 100kW, 20kW to 100kW, 30kW to 100kW, 40kW to 100kW, 50kW to 100kW, 60kW to 100kW, 70kW to 100kW, 80kW to 100kW, or 90kW to 100kW.

[0190] In some embodiments, the output power of the microwave unit can be approximately 10Wt-5kW, 50Wt-5kW, 100Wt-5kW, 150Wt-5kW, 200Wt-5kW, 250Wt-5kW, 300Wt-5kW, 350Wt-5kW, 400Wt-5kW, 450Wt-5kW, 500Wt-5kW, 550Wt-5kW, 600Wt-5kW, 650Wt-5kW, 700Wt-5kW, 750Wt-5kW, 800Wt-5kW, 850Wt-5kW, 900Wt-5kW, 950Wt-5kW, 1kW-5kW, 2kW-5kW, 3kW-5kW, or 4kW-5kW.

[0191] In some embodiments, the output power of the microwave unit can be approximately 10Wt~2.5kW, 50Wt~2.5kW, 100Wt~2.5kW, 150Wt~2.5kW, 200Wt~2.5kW, 250Wt~2.5kW, 300Wt~2.5kW, 350Wt~2.5kW, 400Wt~2.5kW, 450Wt~2.5kW, 500Wt~2.5kW, 550Wt~2.5kW, 600Wt~2.5kW, 650Wt~2.5kW, 700Wt~2.5kW, 750Wt~2.5kW, 800Wt~2.5kW, 850Wt~2.5kW, 900Wt~5kW, 950Wt~2.5kW, 1kW~2.5kW, or 2kW~2.5kW.

[0192] In some embodiments, the adsorbent composite is heated by microwave irradiation to a maximum temperature of approximately 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, 200°C, 225°C, 250°C, 275°C, or 300°C or less.

[0193] In some embodiments, the adsorbent composite is heated by microwave irradiation to a maximum temperature of approximately 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, or 125°C or lower.

[0194] In some embodiments, microwave irradiation heats the adsorbent composite to a maximum temperature of approximately 50°C to 300°C, 75°C to 300°C, 100°C to 300°C, 125°C to 300°C, 150°C to 300°C, 175°C to 300°C, 200°C to 300°C, 225°C to 300°C, 250°C to 300°C, or 275°C to 300°C. In some embodiments, microwave irradiation heats the adsorbent composite to a maximum temperature of approximately 50°C to 150°C, 75°C to 150°C, 100°C to 150°C, or 125°C to 150°C.

[0195] In some embodiments, microwave irradiation can be combined with infrared irradiation, radio frequency irradiation, electromagnetic induction, ultraviolet irradiation, electric heating, and direct heating, or a combination thereof, to heat an adsorption unit containing an adsorption composite material.

[0196] In some embodiments, the irradiation involves irradiating an adsorption unit containing an adsorption composite material with electromagnetic waves in the frequency range of 1 MHz to 300 MHz.

[0197] In some embodiments, the "microwave-transparent" materials described herein, such as microwave-transparent binders, can be transparent to radio frequencies and ultraviolet light.

[0198] In some embodiments, an adsorbent composite material, or an adsorption unit containing an adsorbent composite material, can be irradiated using an alternative energy source other than microwave irradiation to desorb the adsorbed adsorbate. In another embodiment, the adsorption unit containing the adsorbent composite material cannot be housed in a microwave unit. In yet another embodiment, the adsorption unit containing the adsorbent composite material can be subjected to microwave irradiation.

[0199] In some embodiments, an adsorption unit containing an adsorption composite material can be heated by infrared radiation, radio frequency, electromagnetic induction, ultraviolet radiation, electric heating, direct heating, or a combination thereof.

[0200] In some embodiments, an adsorption unit containing an adsorbent composite material can be subjected to radio frequency irradiation in the range of approximately 1 MHz to 300 MHz.

[0201] In some embodiments, an adsorption unit containing an adsorbent composite material can receive radio frequency irradiation at frequencies of 1 MHz to 50 MHz, 100 MHz, 150 MHz, 200 MHz, 250 MHz, or 300 MHz or less.

[0202] In some embodiments, an adsorption unit containing an adsorbent composite material can receive radio frequency irradiation at frequencies of approximately 1 MHz to 300 MHz, 25 MHz to 300 MHz, 50 MHz to 300 MHz, 75 MHz to 300 MHz, 100 MHz to 300 MHz, 125 MHz to 300 MHz, 150 MHz to 300 MHz, 175 MHz to 300 MHz, 200 MHz to 300 MHz, 225 MHz to 300 MHz, 250 MHz to 300 MHz, and 275 MHz to 300 MHz.

[0203] In some embodiments, the adsorbent composite is heated by radio frequency irradiation to a maximum temperature of approximately 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, 200°C, 225°C, 250°C, 275°C, or 300°C or less.

[0204] In some embodiments, the adsorbent composite material is heated by radio frequency irradiation to a maximum temperature of approximately 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, or 125°C or lower.

[0205] In some embodiments, radio frequency irradiation heats the adsorbent composite to a maximum temperature of approximately 50°C to 300°C, 75°C to 300°C, 100°C to 300°C, 125°C to 300°C, 150°C to 300°C, 175°C to 300°C, 200°C to 300°C, 225°C to 300°C, 250°C to 300°C, or 275°C to 300°C. In some embodiments, radio frequency irradiation heats the adsorbent composite to a maximum temperature of approximately 50°C to 150°C, 75°C to 150°C, 100°C to 150°C, or 125°C to 150°C.

[0206] Additional embodiments of the present disclosure relate to systems for adsorbing and desorbing adsorbates, and include the use of adsorbent composites for separating gaseous components from a gaseous mixture in a temperature swing adsorption process.

[0207] In some embodiments, the disclosed system includes an inlet opening, an adsorption unit comprising an adsorbent composite material as described herein, an adsorption unit comprising a fluid inlet and a fluid outlet, a microwave unit housing the adsorption unit, and an outlet opening, the microwave unit being used to irradiate the adsorption unit with microwaves, thereby facilitating the desorption of the adsorbent from the adsorption unit. In some embodiments, the adsorption unit includes a column.

[0208] In some embodiments, a method for manufacturing an adsorbent composite as described herein is provided. In some embodiments, a tubular adsorption column can be manufactured from an adsorbent composite by winding an adsorbent composite sheet having a raised portion into a tubular shape. In some embodiments, a metal rod with threads at both ends is used as a core for initiating the winding of the sheet. In some embodiments, the rod is aluminum. In some embodiments, the rod has a diameter of less than 3 centimeters. In some embodiments, the rod has a diameter of greater than 3 centimeters. In some embodiments, the rod has a length of less than 35 centimeters. In some embodiments, the rod has a length of greater than 35 centimeters.

[0209] In some embodiments, the rod has a diameter of 0.25 cm, 0.35 cm, 0.45 cm, 0.55 cm, 0.65 cm, 0.75 cm, 0.85 cm, 0.95 cm, 1.05 cm, 1.15 cm, 1.25 cm, 1.35 cm, 1.45 cm, 1.55 cm, 1.65 cm, 1.75 cm, 1.85 cm, 1.95 cm, 2.05 cm, 2.15 cm, 2.25 cm, 2.35 cm, 2.45 cm, 2.55 cm, 2.65 cm, 2.75 cm, 2.85 cm, or 2.95 cm. In some embodiments, the rods are approximately 25cm, 25.5cm, 26cm, 26.5cm, 27cm, 27.5cm, 28cm, 28.5cm, 29cm, 29.5cm, 30cm, 30.5cm, 31cm, 31.5cm, 32cm, 32.5cm, 33cm, 33.5cm, 34cm, 34.5cm, or 35cm in length.

[0210] The sheet can be attached to the core using pins that start from the core and penetrate the sheet, or by using an adhesive (e.g., cyanoacrylate). Using a metal core prevents the formation of a bypass channel in the center of the roll with a very small radius of curvature and also facilitates subsequent handling of the roll. In some embodiments, the sheet is wound around the core to a desired diameter to fit the inner diameter of the adsorption column (e.g., a metal pipe). In some embodiments, the winding can be done manually or using a mechanical winding device. The winding is done to a target diameter that may be slightly smaller than the inner diameter of the metal column. In some embodiments, the ends of the roll can be trimmed to form a uniform channel opening, such as a gap 460 as shown in Figure 4.

[0211] In some embodiments, the adsorbent composite roll is inserted into a heat-shrinkable tubing piece made from a polymer capable of withstanding the temperatures expected during use. In preferred embodiments, fluorinated polymers such as FEP can be used for most PSA and TSA applications.

[0212] In a preferred embodiment, the tube is designed to have an initial diameter large enough to accommodate the adsorbent roll, and a final diameter after shrinkage that is slightly smaller than the final roll diameter, thus avoiding excessive compression of the roll during heating for shrinkage. By using a removable mold, it is possible to prevent the ends of the tube from shrinking to a diameter smaller than the diameter of the adsorbent roll. In some embodiments, the length of the shrink tubing is sized to be slightly longer than the axial length of the adsorbent roll to seal the ends. In some embodiments, the assembly is inserted into a metal column, and snap rings are used to firmly press the ends of the shrink tubing against the metal column to prevent process gases from bypassing the flow path. In some embodiments, the snap ring is attached to one end of the roll. In a preferred embodiment, snap rings are attached to both ends of the roll. In some embodiments, the length of the shrink tubing can be trimmed to remove excess material. In some embodiments, to complete the adsorption column, flow distributors (e.g., glass beads) are added to both ends of the column before attaching the end flanges.

[0213] Test method The following describes specific test methods and apparatus, but please understand that other methods or apparatus deemed appropriate by those skilled in the art may be used as alternatives.

[0214] Preparation of adsorbent composite materials

[0215] A series of composite materials containing polytetrafluoroethylene (PTFE) and adsorbent powder were prepared using a general dry mixing method taught in U.S. Patent No. 7,791,861 by Zhong et al. The resulting porous fibrillated adsorbent composites contained adsorbent particles that were durablely intertwined and immobilized within the ePTFE nodes and fibril matrix. Table 1 shows the properties of the various adsorbent composites.

[0216] [Table 1]

[0217] The thickness of the adsorbent composite was measured using a Hitachi scanning electron microscope (SEM) from the top of the raised areas, such as the peaks of the raised areas, to the bottom of the flat surface of the sample. The distance between raised areas was measured at the closest spot between two adjacent raised areas, for example, the valley distance.

[0218] Porosity measurement

[0219] Porosity measurements were performed using a Micromeritics AutoPore V mercury porosimeter (Micromeritics, Norcross, Georgia, USA) with Micromeritics MicroActive software version 2.0. For the test, 99.9995% pure quadruple-distilled virgin mercury (Bethlehem Apparatus, Bethlehem, Pennsylvania, USA) was used as is. The test volume was 5 cm³ per valve. 3 Stem volume 0.392 cm³ 3 A solid-state penetration analyzer (SN: 07-0979) was used. The composite material sample was cut into 1 cm x 2 cm strips, and a sufficient number of these strips were weighed on an analytical balance so that the total mass was approximately 0.25 g. After recording the mass, the sample was placed in the penetration analyzer.

[0220] total porosity

[0221] The total porosity within a substrate such as an adsorbent composite is the value obtained by dividing the void volume of the sample by the total volume of the sample. Porosity can be calculated as follows:

[0222] % porosity = 100 × (Total penetration volume at 60,000 psia (approx. 413.7 MPa)) / (Sample volume at 0.5 psia (approx. 3.5 kPa))

[0223] Table 2 shows the physical properties of typical adsorbent composite materials containing zeolite beads, based on comparative examples.

[0224] [Table 2]

[0225] Pressure drop measurement

[0226] Pressure drop measurements were performed using a vertically positioned column with an inner diameter of 2.5 inches, filled with either 3A composite material or 3A beads. The height of the sample filled with either 3A composite material or 3A beads in the column was 11 inches. Air entered from the bottom of the column and exited from the top, with a surface flow velocity ranging from 0.025 to 1.0 m / s. The air pressure before and after passing through the column was measured using a Magnehelic® differential pressure gauge. The pressure drop was calculated based on the differential pressure (kPa) per meter of sample length.

[0227] Driving conditions 1

[0228] To evaluate water desorption, test adsorbent composites were saturated with moist air (approximately 30% RH) before microwave irradiation. After microwave irradiation, the amount of water desorbed was calculated based on the mass spectrometry signal of water downstream of the structured adsorbent. Microwave irradiation was provided using a 1000W WINIA microwave oven at a frequency of 2.45 GHz.

[0229] Driving conditions 2

[0230] To evaluate the CO2 desorption performance, the test adsorbent composite was pre-saturated with humid air as described in operating conditions 1, and then subjected to microwave irradiation for different durations to remove adsorbed H2O. Group 1 was exposed to microwave irradiation for 75 seconds. Group 2 was exposed to microwave irradiation for a total of 135 seconds (75 seconds and 60 seconds), and Group 3 was exposed to microwave irradiation for a total of 195 seconds (75 seconds and two 60 seconds).

[0231] After H2O desorption, CO2 adsorption was promoted by introducing a 12% CO2 / N2 mixed gas at room temperature into the adsorbent composite material of each test group. After CO2 adsorption, the adsorbent composite material containing zeolite beads or the adsorbent composite material containing PTFE was heated by applying microwaves for 60 seconds, and then CO2 was desorbed.

[0232] Operating conditions 3

[0233] To evaluate complete water desorption, the test adsorbent composite was pre-saturated with moist air (approximately 30% RH) before microwave irradiation. After microwave irradiation, the amount of desorbed water was calculated based on the mass difference before and after microwave irradiation. Microwave irradiation was supplied by a 1000 W WINIA microwave furnace at a frequency of 2.45 GHz. [Examples]

[0234] example Example: Comparative measurement of pressure drop We compared the pressure drop of fluid flows applied to non-limiting embodiments of adsorbent composites containing 3A zeolite as an adsorbent filler and ePTFE as a microwave-permeable binder, or to a packed bed of 3A zeolite beads. As shown in Figure 8, the differential pressure (kPa / meter), i.e., the pressure drop, when passing through the exemplary composite was reduced compared to the pressure drop when passing through the comparison sample of the packed bed of 3A zeolite beads, across a range of surface velocities. At a surface velocity of 0.5 m / s, the pressure drop of the fluid flow applied to the exemplary adsorbent composite was approximately half the pressure drop determined for the fluid flow applied to the packed bed of 3A beads. At a surface velocity of 1.0 m / s, the pressure drop measured in the exemplary adsorbent composite was approximately one-third of the pressure difference measured from the 3A zeolite sample.

[0235] Example: Desorption of adsorbent from an adsorbent composite material containing a microwave-absorbing binder or a microwave-transmitting binder by microwave irradiation. The 13X composite was prepared using a general dry mixing method taught in U.S. Patent No. 7,791,861 by Zhong et al. The resulting porous fibrillated adsorbent composite contained adsorbent particles that were durablely entangled and immobilized within the ePTFE nodes and fibril matrix.

[0236] Zeolite 13X molecular sieve beads are available from Sigma-Aldrich.

[0237] Example 1 The desorption capabilities of adsorbent composite materials containing a microwave-absorbing binder (13X beads) and adsorbent composite materials containing a microwave-transmitting binder (13X composite material) were evaluated in a comparative study of water vapor desorption by microwave irradiation.

[0238] Table 3 shows the chemical composition of the example 13X composite and the comparative 13X zeolite beads. Mineral binders (bentonite) containing Mg, Ca, and Fe were identified in the 13X zeolite beads by energy-dispersive X-ray spectroscopy (Hitachi TM3030 Plus bench microscope). However, no mineral binders were detected in the 13X composite.

[0239] [Table 3]

[0240] Table 4 shows the dielectric properties of bentonite and PTFE. The dielectric properties of bentonite and PTFE were obtained from Ellison et al. (Journal of Microwave Power and Electromagnetic Energy, 2018; 52(1):3-15) and Goyal et al. (Chemical Engineering Journal, 2022; 430(Pt 4): 133183). The loss tangent is the ratio of the dielectric loss coefficient to the dielectric constant. The penetration depth (Pd) is calculated using the following formula.

[0241]

number

[0242] In the formula, λ is the wavelength, ε' is the dielectric constant, and ε'' is the dielectric loss coefficient.

[0243] [Table 4]

[0244] Bentonite, with a dielectric loss coefficient of 0.8 and a loss tangent of 0.27 (greater than 0.1), is considered a high-loss microwave-absorbing material. In comparison, the dielectric loss coefficient and loss tangent of PTFE are approximately three orders of magnitude smaller, making PTFE a low-loss microwave-transmitting material. Bentonite's ability to absorb and dissipate microwave energy is further demonstrated by its penetration depth of 0.042 meters for 2.45 GHz microwaves. In contrast, the penetration depth of 2.45 GHz microwaves through PTFE is approximately 35 meters.

[0245] With the same microwave energy introduction (45 seconds of microwaves), the exemplary adsorbent composite material (13X composite) containing a microwave-permeable binder desorbed approximately 12% more water compared to the adsorbent composite material (13X beads) containing a microwave-absorbing binder, as shown in Figure 9.

[0246] Furthermore, compared to the adsorbent composite containing zeolite beads, the temperature of the adsorbent composite containing PTFE (measured with a FLUKE infrared camera) reached a higher temperature after microwave irradiation (45 seconds of microwave irradiation). Compared to the maximum temperature reached by the adsorbent composite containing 13X zeolite beads (85.5°C), the maximum temperature reached by the 13X composite (98.4°C) increased by approximately 15%.

[0247] Example 2 As determined in Example 1, the desorption capacity of adsorbent composites containing PTFE binders was improved compared to that of adsorbent composites containing mineral binders. Figure 10 shows the comparative CO2 desorption from 13X beads and 13X composites. Across each group, the amount of CO2 desorbed from adsorbent composites containing microwave-permeable PTFE was 20–50% higher than the amount of CO2 desorbed from adsorbent composites (13X beads) containing microwave-absorbing binders. The most significant differences in desorption capacity were observed in groups 1 and 2, where the amount of CO2 recovered from 13X composites was at least twice, or nearly twice, the amount of CO2 desorbed from 13X beads.

[0248] Example 3 The removal of moisture from an exemplary adsorbent composite containing silica as an adsorbent filler and PTFE as a microwave-permeable binder was evaluated over a microwave irradiation range (60-480 kJ). The dry weight of a silica composite containing 85% wt / wt silica was measured after drying in a vacuum oven at 110°C for 16 hours. The amount of absorbed moisture was measured after pre-saturating the silica composite with humid air (approximately 30% RH) before microwave irradiation. The amount of desorbed moisture was measured after microwave irradiation. The percentage of moisture removed was calculated based on the formula: amount of moisture removed / amount of moisture absorbed × 100%. As shown in Figure 11, more than 60% of the moisture was removed after consuming 240 kJ of microwave energy, and 100% moisture removal was achieved at consuming 480 kJ of microwave energy.

[0249] Example - Preparation of an adsorption column from an adsorption composite sheet with raised sections A tubular adsorption column can be fabricated from an adsorbent composite by essentially winding an adsorbent composite sheet with raised sections into a tubular shape. Typically, a metal rod (e.g., an aluminum rod with threads at both ends, 3 / 8 inch in diameter and 11 inches long) is used as the core, and the winding of the sheet begins. The sheet is attached to the core either by perforating it using pins protruding from the core, or by using an adhesive (e.g., cyanoacrylate). Using a metal core prevents the formation of bypass channels in the center of a roll with a very small radius of curvature, and also facilitates subsequent handling of the roll. Next, the sheet is wound around the core to the desired diameter to fit the inner diameter of the adsorption column (e.g., a metal pipe). Winding can be done manually or using a mechanical winding device. The winding is then continued to the target diameter, which is typically slightly smaller than the inner diameter of the metal column. If necessary, the edges of the roll can be trimmed to form uniform channel openings, such as the multiple voids 460 shown in Figure 4.

[0250] Next, the adsorbent composite roll is inserted into a piece of polymer heat-shrink tubing that can withstand the expected temperature during use. Typically, fluoropolymer FEP is a good choice for most PSA and TSA applications. The tubing should be designed so that its initial diameter is large enough to insert the adsorbent roll, and its final diameter after shrinking is slightly smaller than the final roll diameter, to avoid over-compression of the roll during heating for shrinking. Removable molds can be used to prevent both ends of the tubing from shrinking to a diameter smaller than the diameter of the adsorbent roll. The length of the heat-shrink tubing is sized to be slightly longer than the axial length of the adsorbent roll to seal both ends. The assembly is then inserted into the metal column, and snap rings are used to firmly press both ends of the heat-shrink tubing against the metal column to prevent process gases from bypassing the flow path. While it is recommended to use snap rings on both ends of the roll, excellent results can also be obtained by using a snap ring on only one end roll. Finally, the length of the heat-shrink tubing is trimmed to remove any excess. Before attaching the end flanges, complete the adsorption column by adding flow distributors (e.g., glass beads) to both ends of the column.

[0251] The above examples are illustrative and should not be construed as limiting or narrowing the scope of the inventive concept provided by this disclosure. While several embodiments are disclosed, further embodiments will become apparent to those skilled in the art from the following detailed description. This description shows and explains exemplary embodiments. Therefore, the drawings and detailed description should be construed as illustrative, not limiting.

Claims

1. Adsorbent composite material for microwave temperature swing adsorption (TSA), Adsorbent filler, and Microwave-penetrating binder, Includes, The microwave-transmitting binder is an adsorbent composite material having a dielectric loss coefficient of 0.0001 to 0.

1.

2. The adsorbent composite material according to claim 1, wherein the microwave-permeable binder comprises a polymer.

3. The adsorbent composite material according to claim 2, wherein the polymer comprises a hydrocarbon polymer, a fluoropolymer, a polyolefin, or a combination thereof.

4. The adsorbent composite material according to claim 3, wherein the polyolefin comprises a compound selected from the group consisting of polyethylene, polypropylene, ethylenepropylene diene terpolymer, random copolymers comprising at least one propylene group, at least one ethylene group and at least one butene group and / or at least one hexene group, and combinations thereof.

5. The polymers mentioned above include polybenzimidazole (PBI), polyamideimide (PAI), polyimide (PI), polyethersulfone (PES), fluorinated ethylene propylene (FEP), polyetherimide (PEI), polysulfone (PSU), polyamide (PA), cellulose, methylcellulose, cellulose ester, polystyrene (PS), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA or PVOH), polyvinyl butyral (PVB), polyvinyl chloride (PVC), polyvinylpyrrolidone (PVP), polyphenylene sulfide (PPS), and polyfluoroethylene propylene. The adsorbent composite material according to claim 2, comprising compounds selected from the group consisting of polyethylene (PFEP), polyperfluoroacrylate (PPFA), polyvinylidene fluoride (PVDF), terpolymer (THV) of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride, polychlorotrifluoroethylene (PCFE), poly(ethylene-co-tetrafluoroethylene) (ETFE), ultra-high molecular weight polyethylene (UHMWPE), polyparaxylylene (PPX), polylactic acid (PLLA), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), cyclic olefin polymer (COP), cyclic olefin copolymer (COC), their expanded derivatives, and combinations thereof.

6. The adsorbent composite material according to any one of claims 2 to 5, wherein the polymer comprises a compound selected from the group consisting of cellulose, polytetrafluoroethylene (PTFE), polyethylene (PE), polypropylene (PP), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyamideimide (PAI), and polyimide (PI).

7. The adsorbent composite material according to any one of claims 2 to 6, wherein the polymer has a dielectric constant of 1.5 to 4.

8. The adsorbent composite material according to any one of claims 1 to 7, wherein the adsorbent composite material includes one or more self-supporting adsorbent sheets and a parallel-passage type contactor structure having substantially parallel raised portions.

9. The adsorbent composite material according to claim 8, wherein the one or more self-supporting adsorbent sheets are arranged in multiple overlapping layers, spaced apart by substantially parallel ridges, and allowing gas flow between the layers.

10. The adsorbent composite material according to claim 8 or 9, wherein the adsorbent composite material has embossed raised portions.

11. The adsorbent composite material according to any one of claims 8 to 10, wherein each of the one or more self-supporting adsorbent sheets has a thickness of 0.1 to 10 mm and a width of 30 to 1000 mm.

12. The adsorbent composite material according to any one of claims 1 to 11, wherein the microwave-transmitting binder comprises fibrils or a microstructure comprising fibrils and nodes.

13. The adsorbent composite material according to any one of claims 9 to 12, wherein the adsorbent filler is partially or completely embedded in the spaces between the plurality of overlapping layers and / or in at least a portion of the microstructure of the microwave-transparent binder.

14. The adsorbent composite material according to any one of claims 1 to 13, comprising the adsorbent filler in an amount of 10% to 95% (w / w) relative to the total weight of the adsorbent composite material.

15. The adsorbent composite material according to any one of claims 1 to 14, wherein the adsorbent composite material has a total porosity of 30% to 95%.

16. The adsorbent composite material according to any one of claims 1 to 15, wherein the adsorbent filler comprises a high-loss dielectric material (loss tangent greater than 0.1), a low-loss dielectric material (loss tangent less than 0.1), or a combination thereof.

17. The adsorbent composite material according to any one of claims 1 to 16, wherein the adsorbent filler comprises at least one amine group, activated carbon, carbon, graphene oxide, graphite, silica, metal-organic structure, zeolite, alumina, alkali metal oxide, polymer adsorbent, alkali carbonate, ion exchange resin, polyethyleneimine, or a combination thereof.

18. The adsorbent composite material according to claim 17, wherein the adsorbent filler comprising at least one amine group comprises an impregnated amine, an amine supported on a polymer, an amine supported on a metal oxide, an amine supported on carbon, an amine-functionalized polymer, or a combination thereof.

19. The adsorbent composite material according to any one of claims 1 to 18, wherein the adsorbent composite material does not contain a mineral binder.

20. The adsorbent composite material according to claim 19, wherein the mineral binder comprises minerals selected from the group consisting of natural clay, bentonite, attapulgite, kaolin, alumina, silica, gypsum, and combinations thereof.

21. A method for desorbing adsorbate from an adsorption unit containing an adsorbent composite material according to any one of claims 1 to 20, A method comprising irradiating the adsorption unit with electromagnetic waves having a frequency of 1 MHz to 300 GHz, wherein the adsorbate is adsorbed on the adsorbent composite material, and the irradiation promotes the desorption of the adsorbate from the adsorbent composite material.

22. The method according to claim 21, wherein the irradiation includes subjecting the adsorbent composite material to microwaves in the frequency range of 300 MHz to 300 GHz.

23. The method according to claim 21, wherein the irradiation includes subjecting the adsorbent composite material to high-frequency (RF) heating in the frequency range of 1 MHz to 300 MHz.

24. The method according to any one of claims 21 to 23, wherein the adsorbent composite material is housed within the adsorption unit.

25. The adsorbate is hydrogen gas (H 2 ), methane (CH 4 ), carbon monoxide (CO), carbon dioxide (CO) 2 ), water (H 2 O), nitrogen oxides (NO x ), sulfur oxides (SO x The method according to any one of claims 21 to 24, comprising ), volatile organic compounds (VOCs) or a combination thereof.

26. A method for processing fluid flow, To provide a fluid flow, wherein the fluid flow includes an adsorbent. The fluid flow is brought into contact with a device containing the adsorbent composite material described in any one of claims 1 to 20. The adsorbent is adsorbed onto the adsorbent composite material. A method comprising a fluid flow having a temperature of at least -50°C, a surface velocity of 0.1 to 2.0 meters / second, and experiencing a pressure drop of 0.25 to 5 kPa per meter of adsorbent composite material.

27. The method according to claim 26, wherein the fluid flow has a dew point of at least -120°C.

28. The device is irradiated with electromagnetic waves having a frequency of 1 MHz to 300 GHz, and Deposition of the adsorbent, The method according to claim 26 or 27, further comprising:

29. The aforementioned adsorbate is hydrogen gas (H 2 ), carbon monoxide (CO), carbon dioxide (CO 2 ), water (H 2 O), nitrous oxide (N 2 O), nitric oxide (NO), dinitrogen trioxide (N 2 O 3 ), nitrogen dioxide (NO 2 ), dinitrogen pentoxide (N 2 O 5 ), dinitrogen tetroxide (N 2 O 4 ), sulfur dioxide (SO 2 ), sulfur trioxide (SO 3 ), a volatile organic compound (VOC) and combinations thereof, and the single compound is present at a concentration of at least 10 ppb, the method according to any one of claims 26 to 28.

30. The method according to claim 25 or 29, wherein the VOC is selected from the group consisting of benzene, ethylene glycol, formaldehyde, methylene chloride, tetrachloroethylene, toluene, xylene, acetaldehyde, ethane, propane, and 1,3-butadiene.

31. A system for adsorbing and desorbing adsorbates, a) inlet opening; b) an adsorption unit comprising the adsorbent composite material according to any one of claims 1 to 20, c) A microwave unit housing the adsorption unit, Here, the microwave unit is used to irradiate the adsorption unit with microwaves, thereby promoting the desorption of the adsorbent from the adsorption unit, and d) outlet opening; A system that includes this.

32. The system according to claim 31, wherein the adsorption unit includes a column.

33. The system according to claim 31, wherein the adsorption unit includes a plurality of columns.

34. The system according to claim 33, wherein the adsorption unit includes a column array.

35. The system according to claim 33, wherein the column array has a shell-and-tube arrangement or a laminated sheet arrangement.

36. The system according to any one of claims 31 to 35, wherein the adsorption unit further includes at least one fluid inlet and at least one fluid outlet.